Les insuffisances du droit des sociétés de l'OHADA : analyse critique des tensions paradoxales entre innovations réformatrices et pratiques locales, à la lumière du droit français, allemand et de l'Union européenne - Diallo, Mamadou Alimou (Université de Perpignan Via Domitia, 2025)
Il est désormais bien établi que le 17 avril 1997, en application des articles 1 et 2 du Traité portant Organisation pour l’Harmonisation en Afrique du Droit des Affaires (désigné ci-dessous sous l’acronyme OHADA), signé en octobre 1993 à Port-Louis, en l’île Maurice, l’Acte Uniforme relatif au Droit des Sociétés Commerciales et du Groupement d’Intérêt Économique (ci-après AUSCGIE) a été adopté. Présenté à la fin du XXᵉ siècle comme une avancée législative majeure, cet instrument juridique avait pour ambition d’instaurer des dispositions uniformes régissant les sociétés commerciales opérant dans les États membres de l’Organisation. Quinze ans après son adoption, l’AUSCGIE a fait l’objet d’une première révision substantielle. Cette réforme se distingue par son envergure sans précédent en ce sens que plus de 450 dispositions ont été modifiées, tandis que de nouvelles ont été introduites, témoignant ainsi d’une intervention législative d’une rare intensité. Néanmoins, érigée par le discours institutionnel en symbole de modernisation et d’adaptation du droit aux exigences contemporaines, cette réforme soulève de multiples interrogations quant à sa pertinence véritable et à son efficacité pratique. L’étendue des modifications interroge également sur l’adéquation des ajustements aux réalités économiques et juridiques des États membres. En effet, quelques années à peine après cette réforme, des interrogations substantielles ont émergé quant à la reconfiguration du droit des sociétés et aux modalités de sa mise en œuvre. Ces préoccupations révèlent les failles structurelles du nouvel AUSCGIE, en ce qu’elles conduisent à s’interroger sur sa capacité véritable à instaurer un ordre juridique cohérent au sein de l’espace de l’OHADA, apte à discipliner les entreprises dans la réalisation de leur objet social, tout en intégrant les impératifs contemporains de gouvernance durable. Par ailleurs, l’AUSCGIE reflète les tensions structurelles inhérentes à l’idée même d’harmonisation dans un espace caractérisé par des disparités économiques, politiques et institutionnelles persistantes. Cette tension prend une acuité particulière au regard des rapports normatifs que l’OHADA entretient avec d’autres instances régionales, notamment l’UEMOA et la CEMAC. L’uniformisation des règles, loin d’être un processus fluide et homogène, semble entravée par ces clivages qui fragmentent encore l’espace juridique et judiciaire de l’OHADA. L’objectif de ces travaux n’est pas de livrer une exégèse doctrinale purement descriptive de l’AUSCGIE, ni d’en proposer une critique systématique, encore moins dans une dénégation gratuite de l’œuvre normative du législateur de l’OHADA. Il s’agit plutôt, en mobilisant principalement le droit français, allemand et celui de l’Union européenne (UE), d’analyser la pertinence de cette réforme à l’aune des réalités locales et internationales du droit des affaires, afin d’en apprécier l’efficacité et la capacité à répondre aux défis contemporains auxquels les économies africaines sont confrontées. Cette étude s’attache à apprécier la mesure dans laquelle l’Acte uniforme révisé parvient à véritablement répondre aux attentes qu’il a suscitées. Elle vise à confronter la performativité du discours réformateur à la réalité de sa mise en œuvre, en évaluant la capacité effective du texte à encadrer rationnellement l’activité des entreprises, à catalyser les investissements endogènes et à susciter une confiance durable des investisseurs. Ces axes d’investigation, qui articulent la normativité proclamée et la normativité vécue de l’AUSCGIE révisé, constituent le cœur théorique de la présente recherche. Celle-ci se positionne dans une démarche résolument dé-constructive, tendant à dévoiler les apories structurelles, les incohérences téléologiques et les effets de dissonance entre le modèle prescriptif et les pratiques institutionnelles effectives. It is now well established that on April 17, 1997, pursuant to Articles 1 and 2 of the Treaty on the Organization for the Harmonization of Business Law in Africa (OHADA), signed in October 1993 in Port-Louis, Mauritius, the Uniform Act on Commercial Companies and Economic Interest Groups (AUSCGIE) was adopted. Presented at the end of the twentieth century as a major legislative achievement, this legal instrument aimed to establish uniform provisions governing commercial companies and economic interest groups operating within the OHADA member states. Fifteen years post-adoption, the AUSCGIE underwent its first substantial revision during the 35th session of the OHADA Council of Ministers, convened on January 30, 2014, in Ouagadougou, Burkina Faso. This reform, promulgated in the OHADA Official Journal on February 4, 2014, and entering into force on May 5 of the same year, distinguished itself by its unprecedented scope – over 450 provisions were amended, while numerous new stipulations were introduced, reflecting an intervention of exceptional legislative magnitude. Nevertheless, this revision, ostensibly designed to respond to contemporary imperatives for a legal framework balancing modernity, originality, legal certainty, and flexibility, has engendered significant concerns regarding its substantive relevance and practical efficacy. The breadth of these amendments raises critical questions not only about the coherence and stability of the legal framework but also about the congruence of these adjustments with the economic and juridical realities of the member states. Indeed, only a few years after this reform, significant questions emerged concerning the transformation of company law (the AUSCGIE) and the modalities of its implementation. These concerns reveal the structural shortcomings of the new AUSCGIE, as they lead to doubts about its real capacity to establish a coherent legal order within the OHADA area, capable of regulating companies in the pursuit of their corporate purpose while integrating contemporary imperatives of sustainable governance. Furthermore, the AUSCGIE reflects the structural tensions inherent in the very idea of harmonization within a space characterized by persistent economic, political, and institutional disparities. This tension becomes particularly acute when considering the normative relationships that OHADA maintains with other regional organizations, notably UEMOA and CEMAC. The uniformization of rules, far from being a smooth and homogeneous process, appears hindered by these divisions, which continue to fragment the legal and judicial space of OHADA. The purpose of this research is neither to offer a purely descriptive doctrinal exegesis of the AUSCGIE nor to propose a systematic critique, let alone to deny gratuitously the normative achievements of the OHADA legislator. Rather, by drawing mainly on French, German, and European Union (EU) law, it aims to analyze the relevance of this reform in light of both local and international realities of business law, in order to assess its effectiveness and its ability to respond to the contemporary challenges facing African economies. This study seeks to assess the extent to which the revised Uniform Act truly meets the expectations it generated. It aims to confront the performativity of the reformist discourse with the reality of its implementation, by evaluating the text’s actual capacity to rationally regulate corporate activity, to catalyze endogenous investment, and to foster sustainable investor confidence. These areas of investigation, which connect the proclaimed and the lived normativity of the revised AUSCGIE, constitute the theoretical core of the present research. The study adopts a rigorously deconstructive approach, intended to unveil the structural aporias, teleological inconsistencies, and dissonant effects that emerge between the prescriptive model and the institutional practices effectively shaping it
Keywords: AUSCGIE; Acte uniforme révisé; Allemagne; Critical study of the new reform; Droit OHADA; Droit allemand; Droit de l'Union européenne; Droit des sociétés; Droit français; ESG; EU law; France; French law; German law; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'OHADA; Pays de l'Union européenne; Uniform Act on Commercial Companies and Economic Interest Groupings

Vulnérabilité et détresse du chef de TPE-PME : Aspects juridiques et sociétaux - Duplan, Jhonny (Université de Limoges, 2025)
À travers une lecture critique du droit positif, cette thèse propose une analyse de la vulnérabilité des dirigeants de TPE-PME mettant en lumière les limites du droit face aux multiples contraintes de la réalité entrepreneuriale. Il est démontré que la protection juridique actuellement offerte à ces dirigeants demeure partielle, conditionnelle et fragmentaire alors même qu’ils sont confrontés à des faiblesses et à des risques systémiques qui excèdent largement le simple aléa économique. En croisant les enjeux juridiques, économiques et humains, cette recherche vise à parfaire la place du chef de TPE-PME dans l’ordre juridique. Elle appelle à la mise en place d’un cadre plus lisible, équitable, protecteur, accessible et stratégiquement cohérent. Ce cadre doit permettre de restaurer la confiance, prévenir l’effondrement, favoriser le rebond et offrir à ces dirigeants les conditions d’un engagement entrepreneurial à la fois responsable, digne et sécurisé. En mettant en évidence les sources multiples de cette vulnérabilité, ainsi que les faiblesses et risques particuliers auxquels ces opérateurs économiques sont exposés dans la gestion quotidienne de leurs activités, cette analyse constitue un plaidoyer en faveur de la reconnaissance et/ou de l’attribution de la qualité de personne vulnérable à ces sujets de droit. Through a critical reading of positive law, this thesis offers an analysis of the vulnerability of SME (Small and Medium-sized Enterprise) leaders, highlighting the limitations of the legal system in addressing the numerous constraints of entrepreneurial reality. It demonstrates that the current legal protection afforded to these leaders remains partial, conditional, and fragmented, even though they face weaknesses and systemic risks that go far beyond mere economic uncertainty. By interweaving legal, economic, and human dimensions, this research seeks to redefine the role of the SME leader within the legal order. It calls for the establishment of a clearer, fairer, more protective, accessible, and strategically coherent legal framework. Such a framework should help restore confidence, prevent collapse, support recovery, and provide these leaders with the conditions for responsible, dignified, and secure entrepreneurial engagement. By shedding light on the multiple sources of this vulnerability, as well as the specific weaknesses and risks faced by SME leaders in the day-to-day management of their businesses, this analysis serves as an argument in favor of recognizing – or granting – the status of legally vulnerable persons to these economic actors.
Keywords: Bounce back; Chef de TPE-PME; Distress; Détresse; Head of the company; Petites et moyennes entreprises; Rebond; Resilience; Résilience; Small business owner; TPE-PME; Vulnerability; Vulnérabilité

Le contentieux des pactes d'associés - Lechêne, Jules (Université Paris Sciences et Lettres, 2025)
Cette thèse propose une analyse renouvelée du contentieux des pactes d’associés en l’appréhendant comme un risque juridique structurel, et non comme une simple contingence factuelle. L’étude met d’abord en lumière la fonction particulière des pactes, entendus comme instruments de couverture de l’aléa social qui traversent le contrat de société. Les engagements qu’ils contiennent – mécanismes de transfert de droits sociaux ou stipulations permettant d’exiger un comportement – révèlent toutefois des fragilités propres, susceptibles de nourrir des contestations au moment de leur mise en œuvre. L’analyse systématise alors les voies de remise en cause possibles et montre que le risque contentieux dépend autant des mécanismes juridiques en cause que de la compétence des parties à activer ou non ce contentieux. Face à ce constat, la recherche élabore un modèle contractuel de traitement du risque contentieux, fondé sur la notion autonome de contrainte, exercée à destination des parties ou du juge. Par des techniques telles quel a renonciation, les prérogatives d’interprétation, les accords de qualification ou de régime, ce modèle permet d’anticiper et d’encadrer les contestations. Appliqué aux différents types d’engagements rencontrés dans les pactes d’associés, ce modèle démontre sa pertinence tout en révélant les frontières de la contractualisation. Il ne supprime pas toute possibilité de litige, mais permet d’en saisir la logique et d’en proposer un traitement structuré dès l’origine du contrat. This thesis offers a renewed analysis of litigation arising from shareholders’ agreements by approaching it as a structural legal risk, and not as a mere factual contingency. The study first highlights the particular functionof such agreements, understood as instruments for covering the social uncertainty that runs through the company contract. The commitments they contain – mechanisms for the transfer of shares or stipulations requiring a certain behaviour – nevertheless reveal their own fragilities, likely to fuel disputes at the time of their implementation. The analysis then systematises the possible avenues for challenge and shows that litigation risk depends as much on the legal mechanisms involved as on the parties’ ability to activate or not activate such litigation.In response to this observation, the research develops a contractual model for the treatment of litigation risk,based on the autonomous notion of constraint, exercised either towards the parties or towards the judge.Through techniques such as waiver, interpretative prerogatives, and qualification or regime agreements, this model makes it possible to anticipate and frame potential disputes.Applied to the different types of commitments found in shareholders’ agreements, this model demonstrates its relevance while revealing the boundaries of contractualisation. It does not eliminate all possibilities of litigation, but enables one to grasp its logic and to propose a structured treatment from the very origin of the contract.
Keywords: Accord; Agreement; Behaviour; Comportement; Contentieux; Contract; Contractual constraint; Contrainte contractuelle; Contrat; Corporate law; Droit des sociétés; Droits sociaux; Interpretation; Interprétation; Litigation; Litigation risk; Pacte d'associés; Pacte d’actionnaires; Prerogative; Prérogative; Qualification; Regime; Risque contentieux; Régime; Shareholders' agreement; Shares; Transfer; Transfert

L'associé salarié - Brenn, Chloé Le (CY Cergy Paris Université, 2025)
L'associé salarié est aujourd'hui une figure répandue dans le paysage juridique, en dépit d'une contradiction évidente : il est à la fois propriétaire du capital et subordonné à la société qui l'emploie. Cette antinomie apparente et les interrogations qui en découlent apparaissent, pourtant, majoritairement passées sous silence. Le cumul des qualités d'associé et de salarié est ainsi admis par principe, notamment depuis l'avènement des dispositifs légaux d'actionnariat salarié.Ce silence nourrit l'opportunité d'une étude approfondie de la figure de l'associé salarié. Une analyse miroir du droit des sociétés et du droit du travail est à même de vérifier la réelle compatibilité de ces qualités, tant au niveau de la licéité du cumul que des règles qui lui sont applicables. La proposition est la suivante : se plonger dans l'analyse chronologique du cumul des qualités d'associé et de salarié, de sa naissance à sa disparition, par une étude combinée du droit du travail et du droit des sociétés.En ressort une compatibilité relative des qualités tenant davantage à l'influence du droit du travail que du droit des sociétés. Ce constat ne doit cependant pas minimiser les influences réciproques des deux branches du droit. Contrairement au postulat qui semble suivi par une majorité d'auteurs, l'associé salarié n'est pas juste un salarié particulier : il est également un associé singulier. The employee shareholder is now a commonplace figure, despite a major contradiction: he is both owner of the capital and subordinate to the company that employs him. This apparent conflict and the questions it raises are largely ignored. The dual status of shareholder and employee is accepted as a matter of principle, particularly since the advent of legal employee share ownership schemes.This silence provides an opportunity for a study of the situation of the employee shareholder. A mirror analysis of company law and labour law is able to study the real compatibility of these qualities, simultaneously of the lawfulness of the combination and the rules applicable to it. The proposal is: to analyse in chronological order the dual status of shareholder and employee, from its inception to its demise, by a combined study of labour law and company law.A relative compatibility of these roles emerges. It is due more to the influence of labour law than company law. However, this observation should not minimise the reciprocal influences of the two branches. Contrary to the assumption that seems to be followed by some authors, the employee shareholder is not just a particular employee: he is also a singular shareholder.
Keywords: Actionnariat salarié; Associé; Associé salarié; Corporate law; Droit des sociétés; Droit du travail; Employee; Employee shareholder; Labor law; Salarié; Shareholder

L'absorption d'une personne morale membre d'un conseil d'administration : étude comparée - Diomande, Yannick (Université de Bordeaux, 2024)
L’opération de fusion-absorption d’une personne morale est une question en soi difficilement appréhendée tant dans les effets qu’elles déploient que dans l’organisation d’une telle opération. Cette difficulté propre à la nature d’une telle opération prendra une allure tout autre lorsqu’une personne morale membre d’un conseil d’administration s’y trouve impliquer. Toutes les hypothèses pouvant être développées traduisent non seulement la diversité mais également la complexité d’un tel sujet. Si cette question telle qu’elle est évoquée, est révélatrice du caractère instrumental du droit des sociétés, force est de reconnaître que la résolution d’une telle problématique devrait se faire par la conciliation des caractéristiques propres au droit des fusions mais aussi en tenant compte des spécificités entourant la personne morale administrateur. La transmission universelle du patrimoine, la réorganisation des pouvoirs post-fusion, les droits des créanciers, le problème de la représentation de la personne morale dans la société absorbante, la gouvernance de la société administrée, l’intrusion d’une personne morale tierce, les questions de fusions internationales sont autant de questions soulevées par cette problématique. La solution de cette problématique commande une étude minutieuse des questions soulevées à l’aune du droit OHADA et du droit français.
Keywords: Absorbed legal person; Absorbing legal person; Commercial companies; Companies with board of directors; Conseil d'administration; Corporate law; Droit des sociétés; Droit des sociétés commerciales; France; Fusion-absorption; Merger; Pays de l'OHADA; Personne morale absorbante; Personne morale absorbée; Personnes morales; Restructuration; Restructuring; Études comparatives

La notion d’apport en nature dans les sociétés de capitaux - Ellaji, Abderrazak (Le CNAM, 2024)
La notion d’apport en nature revêt des enjeux d’une grande complexité, tant sur le plan juridique que pratique. Elle soulève de nombreuses difficultés d’interprétation et de mise en œuvre. Celles-ci sont exacerbées par l’essor de la diversité des biens et droits susceptibles d’être apportés en société, ainsi que par la multiplicité des modes de rémunération des associés. Cependant, cette évolution n’a pas été suffisamment suivie par le législateur et la contribution d’une partie importante de la jurisprudence et de la doctrine antérieures est devenue quasi obsolète. Face à cette problématique émergente, un renouvellement du contour juridique de la notion d’apport en nature dans toutes ses dimensions est devenu une nécessité impérieuse.Cette thèse propose une approche globale de la notion d’apport en nature. Cet apport peut être effectué à titre particulier, permettant ainsi la réintégration d’un ou plusieurs actifs ou activités utiles au développement de la société. En outre, le délestage d’un actif non nécessaire à l’exploitation, par voie d’apport, est également possible. Toutefois, le régime juridique de droit commun auquel est soumis cet apport peut s’avérer inapplicable en raison de restrictions de nature légale ou contractuelle. Dans ce contexte, l’apport à titre universel constitue une solution pertinente pour surmonter cette contrainte. Cet apport concerne notamment les opérations de fusion, de scission et d’apport partiel d’actifs et se concrétise toujours par une transmission universelle de patrimoine, dont les enjeux et conséquences sont examinés en profondeur dans la présente étude.Ce travail aborde également le paradoxe lié à l’évaluation de l’apport en nature et aux modes de rémunération et tente de mettre en évidence une synthèse des insuffisances du cadre législatif et doctrinal entourant le sujet. Il propose ainsi des alternatives envisageables pour surmonter les contraintes inhérentes à la réalisation de certaines opérations d’apport. Restent d’autres situations, dans lesquelles l’intervention du législateur apparaît nécessaire pour contourner les contraintes mises en évidence dans l’étude.
Keywords: Apport en capital; Apport en nature; Apports (droit commercial); Contribution in kind; Contribution to a capital company; Entreprises (réorganisation); Fusion d'entreprises; Fusion des sociétés; Merger of companies; Restructuration des sociétés; Restructuring of companies

Les entreprises de tendance - Delyfer, Anne-Marie (Université Paris 10, 2024)
Contrairement aux entreprises dites "classiques", qui ont pour objectif principal la production de biens ou de services dans un cadre lucratif, l'entreprise de tendance est une catégorie juridique et sociale à part. Sa spécificité ne réside pas dans la recherche de profits, mais dans la promotion et la défense de convictions, qu'elles soient religieuses, politiques, ou philosophiques. Cette dimension convictionnelle distingue ces entreprises des autres et impose de définir avec précision leurs contours, car toutes ne peuvent pas revendiquer ce statut. L'entreprise de tendance n’est donc pas un modèle d'entreprise ordinaire. Au cœur de son fonctionnement se trouvent des valeurs et des croyances qui façonnent non seulement son activité mais aussi son identité. Ce type d’entreprise devient un instrument au service d'une idéologie ou d'une foi, portant un message à la société et jouant un rôle crucial dans le maintien du pluralisme idéologique dans une démocratie. Cependant, la reconnaissance juridique des entreprises de tendance varie largement d’un pays à l’autre, en fonction de l’histoire, des sensibilités sociétales et du cadre législatif.La manière dont les États reconnaissent et encadrent les entreprises de tendance reflète leur conception de la place des convictions religieuses ou politiques dans l'espace public. En fonction de cette reconnaissance sociale et légale, ces entreprises peuvent bénéficier de régimes juridiques particuliers, tant dans leurs relations avec les salariés qu’en matière de financement. Cette reconnaissance variable, ainsi que les privilèges qui peuvent en découler, doivent être analysés, notamment à l'aune des décisions des Cours européennes.
Keywords: Convictions; Employees; Employer; Employeur; Employé; Entreprise de tendance; Ideological; Ideological organization; Idéologie; Idéologique; Relationships; Salariés

Le remboursement des apports en société - Elzahar, Nada Morsy (Université Paris 1, 2024)
Le remboursement des apports en société est l’une des notions utilisées fréquemment juridiquement, mais qui n’est pas définie ni par la loi ni par la jurisprudence ; il n’existe pas un régime juridique, indépendant et délimité, qui l’encadre. De plus, un nombre limité d’auteurs ont fourni des définitions pour le remboursement des apports qui ne sont pas même unifiées. Ils ont aussi fait référence à la restitution des apports souvent dans le même contexte, sans établir une distinction entre les deux termes « remboursement » et « restitution ». Avec l’absence d’une définition précise de remboursement des apports, les questions se posent : si d’après le régime juridique applicable dans le cadre des sociétés, il existe une obligation de restitution des apports qui va se varier selon le type de l’apport en cause ; ou le remboursement de l’apport constitue le paiement d’une obligation, autre que celle d’une restitution. Notamment, à la lumière de la relation entre l’apport et le capital social en vertu de laquelle les titres sociaux sont eux qui représentent les différents droits de l’associé et le montant du capital social est celui qui représente la dette de la société et l’ensemble des créances des associés. L’étude fournit ainsi une identification des éléments caractéristiques de remboursement des apports en société. Elle fournit également une identification de ses éléments perturbateurs, en abordant la question d’éventuelle manifestation de remboursement des apports au cours de la vie sociale, et en analysant le statut original de l’apporteur en industrie dont l’apport ne fait pas juridiquement l’objet de remboursement. The reimbursement of the contributions to a company is one of the notions frequently used in legal contexts, but it has not been defined either by law or by jurisprudence. There is no independent and defined legal regime governing it. Moreover, only a limited number of authors have provided definitions of the reimbursement of contributions that are not even unified. They have referred to the restitution of contributions, always in the same context, without making the distinction between the two terms "reimbursement" and "restitution". With the absence of a precise definition of the reimbursement of contributions, questions arise: according to the applicable legal regime for companies, does an obligation of restitution of contributions, varying according to the type of contribution, exist, or is the reimbursement of contributions the payment of an obligation other than restitution? These questions are especially relevant in light of the relationship between contributions and capital, under which shares represent the different rights of the partners and the amount of the capital represents the debt of the company. Thus, the study provides an identification of the characteristic elements of the reimbursement of contributions to a company. It also identifies its disruptive elements by addressing the eventual manifestation of the reimbursement of the contributions during the life of the company, and by analyzing the distinct status of a partner who has made a contribution in industry, which is not legally subject to reimbursement.
Keywords: Apport; Capital; Capital social; Contribution; Dissolution de la société; Dissolution of the company; Droit des sociétés commerciales; Monetary obligation; Obligation de somme d'argent; Paiement; Payment; Rachat des titres par la société; Repurchase of shares by the compan; Restitution; Shares; Titres sociaux

La liberté d'établissement intracommunautaire des sociétés commerciales dans les espaces de la CEDEAO et de l'Union Européenne - Kpatindé, Métogbé (Université de Perpignan Via Domitia, 2024)
Les sociétés commerciales dans un espace communautaire sont amenées à développer ou délocaliser leurs activités dans d'autres pays membres que celui dans lequel où elles sont originairement installées. La liberté d'établissement régit le droit pour une société de s'installer dans un autre État membre et d'y exercer une activité de façon durable. C'est notamment le cas lors des délocalisations, des opérations de fusions-acquisitions, de création de filiales, ou de représentation à l'étranger. C'est le cas aussi dans le transfert de siège social. Chaque société commerciale agit selon les règles juridiques de l'État où elle est établie. Dès lors qu'elle étend, déplace ses activités ou effectue des opérations dans plusieurs États, elle engendre automatiquement des éléments d'extranéité et se trouve confrontée à des questions spécifiques telles que celles de sa reconnaissance dans un État étranger, de la loi qui lui est applicable ou de sa nationalité. Cette mobilité entraîne aussi le changement de son environnement juridique. Désormais c'est dans un autre droit des sociétés qu'elle se meut. Toutes les matières du droit des sociétés se trouvent affectées : les droits fiscaux, sociaux, environnementaux, le droit du travail, le droit comptable, etc. Dans leurs textes fondateurs, les deux espaces communautaires que sont la Communauté Économique des États de l'Afrique de l'Ouest (CEDEAO) et l'Union Européenne (EU) consacrent ce principe de la liberté d'établissement au profit des sociétés. Bien que le but recherché par les législateurs africains et européens soit l'intégration économique, ce principe soulève néanmoins certaines questions et difficultés relatives à la mise en œuvre des normes communautaires. Contrairement aux pays membres de la CEDEAO qui ont pour socle technique d'uniformisation de leur droit interne l'OHADA (Organisation pour l'Harmonisation en Afrique du Droit des affaires) les pays de l'Union Européenne, eux, ne disposent pas de cadre juridique intégré, ce qui multiplie les difficultés pour la mobilité des sociétés au sein de l'espace communautaire européen. Commercial companies in a community space are often required to develop or relocate their activities to other Member States than the one in which they are originally established. Freedom of establishment is the right for a company to establish itself in another Member State and to carry on business there in a sustainable manner. This is particularly the case for relocations, mergers and acquisitions or the setting up of subsidiaries. It is also the case when the head office is transferred. Commercial companies operate according to the legal rules of the State where they have been settled. Every company considering expansion into another Member State is likely to generate foreign elements and to face specific issues such as its recognition in the foreign State, the law applicable to it or its nationality. The entire legal environment might change and all branches of corporate law can be affected: tax, social, environmental, labour, accounting and other laws. In their founding texts, the two Community spaces, the Economic Community of West African States (ECOWAS) and the European Union (EU), enshrine this principle of freedom of establishment within their Member States. Even though the goal pursued by African and European legislators is economic integration, this principle nevertheless raises a number of issues and serious questions relating to the implementation of Community standards. Unlike the ECOWAS member States, which have OHADA (Organization for the harmonization of business Law in Africa) as an existing basis for the unification of their domestic business law, members States of the European Union do not have a unified legal framework, which increases the issues a company must face in its mobility processes within the European Community space
Keywords: Business mobility; CEDEAO; Commercial companies; Corporate law; Droit des sociétés; ECOWAS; European union; Freedom of establishment; Liberté d'établissement; Mobilité des sociétés; OHADA; Pays de l'OHADA; Pays de l'Union européenne; Sociétés commerciales; Union europeenne

A comparative appraisal of creditor protection mechanisms under South African company law - Sibanda, Mandhlaenkosi (University of South Africa, 2024)
The study comparatively scrutinised creditor protection mechanisms entrenched in South African Corporate law to determine their effectiveness in advancing creditor interests in company affairs. The enquiry was triggered by the need for corporate laws to adapt to and align with the pace of global economic changes in open and democratic societies. The 2004 DTI Policy document on South African Corporate Law Reform (SACLR) proposed a shift from the traditional shareholder-centric view, which espouses shareholder importance in corporate governance, to a model that retains the supremacy of shareholder interests while simultaneously catering to the interests of other stakeholders (the enlightened shareholder value approach). In light of the DTI policy proposal, the parliament, in enacting the South African Companies Act 71 of 2008 (the Companies Act), reflected on the need to provide appropriate redress to investors' and third parties (creditors`) rights in the preamble to this piece of legislation. It was based on the forgoing expositions that this research work sought to establish whether the South African Corporate law had been adequately modelled to protect creditors and to look beyond the traditional company’s goal of profit maximisation for the shareholder at the expense of other stakeholders, such as the creditors, who equally have stakes in the success and continuation of the company. Thus, a comparative doctrinal and critical analysis of creditor protection laws from selected cognate jurisdictions was undertaken to determine the efficacy of the protection mechanisms accorded to creditors under the South African corporate jurisprudence. It is thus the researcher's findings that the South African provisions on mechanisms to protect creditors are set in motion and are, therefore, effective to a greater extent, subject to legislature dealing with some discrepancies as per lessons drawn from comparator jurisdictions and recommendations. Conclusively, the Companies Act should clearly include the creditor’s interests in those of the company and thus give a secondary duty to directors to ensure creditor interests, among other non-member stakeholders, are assertively safeguarded.
Keywords: Company controllers; Company law; Corporate entity; Corporate law; Corporate veil; Credit systems; Creditor interests; Creditor protection mechanisms; Creditors; Directors; Employees; Investors; Shareholders; Stakeholder constituencies; Stakeholder interests; Stakeholders; Third parties

La variabilité du capital social en droit OHADA à la lumière du droit français - Ouoba, Lambouado Raymond (Université de Perpignan Via Domitia, 2024)
Le législateur OHADA s'est inspiré du droit français pour fixer le cadre juridique de la variabilité du capital social ; d'où l'étude orientée vers une approche comparatiste. Cette approche a permis une confrontation entre deux (02) systèmes juridiques, en vue de dégager les problèmes de droit et d'envisager une amélioration du cadre juridique de la variabilité du capital en droit OHADA ; l'objectif étant de dégager une contribution à l'amélioration du droit OHADA à travers le droit comparé. A l'analyse, il ressort que la variabilité du capital social comporte des facteurs attractifs pour les acteurs économiques. En effet, elle constitue un mécanisme de financement des sociétés, en raison d'une part, de sa capacité à renforcer les capitaux propres sans charge financière et, d'une part, de sa capacité à constituer un actionnariat spécifiquement orienté sur la rentabilité des sociétés. De même, elle pourrait susciter un intérêt pour les investisseurs intéressés par la célérité et l'efficacité dans les opérations de financement des entreprises. L'efficacité du financement de la société par la mise en œuvre de la clause de variabilité du capital est tributaire, entre autres, de son attractivité auprès des acteurs économiques de manière générale, des investissements et des professionnels du droit en particulier. Cependant, plusieurs facteurs ne militeraient pas en faveur du recours à la variabilité du capital. Parmi ces facteurs figurent les risques découlant de la réduction du capital et la méconnaissance des acteurs économiques et des praticiens du droit de l'existence et/ou du fonctionnement du mécanisme de la variabilité du capital. Or, ces risques ne sont pas irrémédiables, dans la mesure où il existe des mécanismes juridiques appropriés pour y faire face. En somme, l'analyse du fonctionnement du mécanisme de la variabilité du capital social a mis en évidence ses capacités de mobilisation de financement, de recapitalisation de la société, de restructuration de la société et d'apporter une contribution à l'amélioration du cadre juridique des sociétés à capital variable. Elle a également permis de démontrer l'insuffisance de la justification ou du fondement du désintérêt des acteurs économiques et des praticiens du droit à l'égard de la variabilité du capital social
Keywords: Approche comparée; Augmentation de capital; Capital increase; Capital reduction; Capital social; Droit OHADA; Droit français; French Law; OHADA Law; Réduction de capital; Share capital; Sociétés à capital variable

Anonim şirketlerde yönetim kurulu iç yönergesi - İlgün Çamli, Zehra (Kırıkkale Üniversitesi, 2024)
Anonim şirket organları, özel hukuktaki sözleşme özgürlüğünün bir sonucu olarak kendi yetki alanlarına giren konuları iç yönerge ile düzenleyebilirler. Anonim şirket yönetim kurulu da yetki alanına giren konularda iç yönerge çıkarmak suretiyle düzenleme yapabilir. Türk Ticaret Kanunu'nda yönetim kurulunun yönetim yetkisini devrettiği ve sınırlı yetkili ticari vekil ve diğer tacir yardımcıları atadığı durumlarda bu işlemleri bir iç yönerge çıkararak gerçekleştirmesi zorunlu tutulmuştur. Bununla birlikte anonim şirket yönetim kurulu iç yönergesinde iç yönerge çıkarma zorunluluğu doğuran bu iki durum dışında yetki alanına giren diğer birçok konuyu düzenleyebilir. Bu kapsamda belirli durumlarda çıkarılması zorunlu olan bu iç yönergelerin zorunlu içeriğinin dışında, iç yönergede, yönetim kurulunun görevleri, çalışma usulü, yönetim kurulu üyelerinin ve yönetim yetkisinin devredildiği kişilerin hak ve yükümlülükleri gibi birçok husus yer alabilir. Bu düzenlemelerin sınırını da ilk başta Türk Ticaret Kanunu ve diğer kanunların emredici hükümleri oluşturur. Yönetim kurulunun Türk Ticaret Kanunu'nda çizilen yetki sınırları da bu çerçevede yönetim kurulu iç yönergesinin azami içeriğini belirler. Çalışmamızın ilk bölümünde anonim şirketlerde iç yönerge terimi açıklanmaya çalışılmış, ardından yönetim kurulu iç yönergesi terimi yetki devrinden ve sınırlı yetkili ticari vekil ve diğer tacir yardımcısı atanmasından bağımsız şekilde yönetim kurulunun çıkardığı düzenleyici bir metin olarak ele alınmıştır. Çalışmamızın ikinci bölümünde anonim şirket yönetim kurulu iç yönergesinin içerebileceği düzenlemeler ve bunların iç yönergede ne şekilde düzenlenebileceği incelenmiştir. Çalışmamızın son bölümünde ise yönetim kurulunun kendi çıkardığı iç yönergeyi ihlal etmesinin sonuçları gibi iç yönergeye ilişkin diğer meseleler ele alınmıştır. The organs of a joint stock company, as a result of the freedom of contract in private law, can regulate matters within their jurisdiction through internal directives. The board of directors of a joint stock company can also regulate matters within its jurisdiction by issuing internal directives. According to the Turkish Commercial Code, it is mandatory for the board of directors to execute transactions, such as delegating management authority and appointing limited authority commercial representatives and other merchant assistants, through the issuance of an internal directive. However, beyond these two instances where issuing an internal directive is mandatory, the board of directors can regulate many other matters within its jurisdiction through an internal directive. In this context, aside from the mandatory content in specific situations, an internal directive can include many issues such as the duties of the board of directors, working procedures, and the rights and obligations of board members and those to whom management authority has been delegated. The boundaries of these regulations are primarily determined by the mandatory provisions of the Turkish Commercial Code and other laws. The authority limits outlined in the Turkish Commercial Code also define the maximum content of the board's internal directive. In the first part of our study, the term "internal directive" in joint stock companies is explained. Subsequently, the term "internal directive of the board of directors" is examined as a regulatory document issued by the board, independent of authority delegation and the appointment of limited authority commercial representatives and other merchant assistants. In the second part of our study, the potential regulations that could be included in the internal directive of the board of directors of a joint stock company and how these can be arranged within the internal directive are analyzed. In the final part of our study, other issues related to internal directives, such as the consequences of the board of directors violating its own internal directive, are discussed.
Keywords: Authority of the Board of Directors; Board of directors; Delegation of Management; Droit des sociétés commerciales; Internal Directive; Limited Authority Commercial Representative; Sınırlı Yetkili Ticari Vekil; Working Procedures of the Board of Directors; Yönetim Kurulu; Yönetim Kurulunun Yetki Alanı; Yönetim Kurulunun Çalışma Usulü; Yönetimin Devri; İç Yönerge

Anonim şirkette imtiyazlı pay sahipleri özel kurulu - Yilmaz, Hümeyra (İstanbul Üniversitesi, 2024)
Bu doktora tezi, 6102 sayılı Türk Ticaret Kanunu'nun 454. maddesinde düzenlenen imtiyazlı pay sahipleri özel kurulunu konu almaktadır. Çalışmanın ilk bölümünde imtiyaza ilişkin genel bilgiler verildikten sonra ikinci bölümünde imtiyazlı pay sahipleri özel kurulunun yapısı, yetkisi, hukuki niteliği üzerinde durulmuştur. Çalışmanın üçüncü ve dördüncü bölümlerinde, imtiyazlı pay sahipleri özel kurulunun toplanma şartları ile toplantı süreci kapsamlı bir şekilde ele alınmıştır. Çalışmanın son bölümünde ise imtiyazlı pay sahipleri özel kurul kararlarının hukuki niteliği, etkisi ve hükümsüzlüğü irdelenmiştir. Çalışmanın hazırlanmasında, Türk hukukundaki ilgili mevzuat hükümleri başta olmak üzere karşılaştırmalı hukuktaki dikkate değer yasal düzenlemeler, öğretideki görüşler ve yargı kararlarından faydalanılmıştır. Anahtar kelimeler: Anonim şirketler, imtiyaz, TTK m. 454, imtiyazlı pay, imtiyazlı pay sahipleri özel kurulu. This doctoral thesis deals with the special committee of privileged shareholders regulated under Article 454 of the Turkish Commercial Code No. 6102. After giving general information about privilege in the first part of the study, the structure, authority, and legal nature of the special committee of privileged shareholders are mentioned in the second part. In the third and fourth parts of the study, the conditions for the meeting and the meeting process of the special committee of privileged shareholders are extensively discussed. In the last part of the study, the legal effect, nature, and invalidity of the special committee decisions of privileged shareholders are examined. In the preparation of the study, notable legal regulations in comparative law, doctrines and judicial decisions, especially related legislation in Turkish law have been benefited from. Key Words: Joint Stock Companies, privilege, the article 454 of the Turkish Commercial Code No. 6102, privileged share, the special committee of privileged shareholders.
Keywords: Anonim şirketler; Joint stock company; Special meeting; Turkish commercial law; Türk ticaret hukuku; Özel kurul

An analysis of merger and amalgamation transactions under the Companies Act 71 of 2008 and the Income Tax Act 58 of 1962 - Meyer, Carolina (University of Pretoria, 2023)
In law it is common to encounter two separate pieces of legislation which govern a single matter or transaction, for example, the Companies Act 71 of 2008 (the Companies Act) and the Securities Transfer Act 25 of 2007 both of which address the sale of shares. Similarly, the Income Tax Act 58 of 1962 (the Income Tax Act) and the Companies Act both have regulations which govern, respectively, tax law and company law matters in South Africa. These two Acts overlap in various business and commercial fields as tax is frequently an important component of any business transaction undertaken by a company. Issues, however, arise when the regulations in these two Acts, are inconsistent. This can be observed if one compares the current South African Income Tax and Companies Act, specifically as regards the sections involving merger and amalgamation transactions. Section 44 of the Income Tax Act governs merger and amalgamation transactions from a tax perspective and provides for tax rollover relief if certain requirements are met. The regulations governing mergers and amalgamations under the Companies Act are contained in sections 113, 115 and 116 of the Act. Although these sections in both Acts address the same transaction – a merger or amalgamation between two or more companies – there are several discrepancies between the regulations in the two Acts which appear to operate entirely independently of one another. In practice, one often sees that other sections in the Companies Act and Income Tax Act are used to achieve a merger due, in the main, to the uncertainties in the application of the relevant merger sections in the two Acts and the limited interaction between them. This study identifies and assesses the impact of the discrepancies identified in these two Acts in relation to merger and amalgamation transactions. The study makes recommendations to address these discrepancies and to align the South African Companies Act and Income Tax Act as regards merger/amalgamation transactions.
Keywords: Amalgamation; Companies Act; Income Tax Act; Merger; Taxation

مدى تأثر الشركة بانسحاب الشريك (دراسة مقارنة) - شريفي, ويزة (جامعة مولود معمري, 2023)
تهدف دراسة موضوع انسحاب الشريك في القانون الجزائري والقانون المقارن إلى تحديد التنظيم القانوني لعملية انسحاب الشريك من الشركة، والوقوف على أسباب ومبررات عملية الانسحاب، وأهم الوسائل المتاحة لتحقيقه، خاصة وأنّ آثار الانسحاب تنصرف أساسا إلى الشريك المنسحب، كما تمتدإلى الشركة والشركاء والغير الذي تعامل مع الشركة. وقد أثبتت الدراسة المقارنة في القانونين الجزائري والفرنسي، مدى تأثر القانون الجزائري بالقانون الفرنسي، بسبب غياب تنظيم قانوني خاص في التشريع الجزائري لمسالة انسحاب الشريك من الشركة. ونتيجة لهذا الفراغ القانوني، استوجب الرجوع إلى القواعد العامة في القانون المدني، الذي ينظم عقد الشركة بصفة عامة، مع الأخذ بعين الاعتبار خصوصية الشركات التجارية والأحكام الخاصة المنظمة لها. إنّ انسحاب الشريك، قد يكون إراديًا في حالة قيامه بالتخلّي عن حقوقه الاجتماعية في الشركة، وقد يكون الانسحاب لا إراديا، عندما يكون عن طريق حكم قضائي، بحيث يتم في هذه الحالة إنهاء مهام الشريك من دون إرادته. وكقاعدة عامة، فإن انسحاب الشريك يِؤدي حتما إلى انقضاء الشركة، لاسيما إذا تعلق الأمر بشركات الأشخاص، إلا إذا كانت القوانين الأساسية للشركة والشركاء الباقون، قد قرروا خلاف ذلك، بمعنى استمرار الشركة. L’étude du retrait de l’associé en droit algérien et droit comparé a pour but de déterminer la réglementation juridique du mécanisme du retrait de l’associé de la société, afin de mettre l’accent sur les motifs du retrait, les moyens et techniques juridiques pour y parvenir, mais surtout ses effets, car le retrait touche principalement les droits de l’associé, les partenaires associés, et enfin les tiers. L’étude comparative du droit algérien et français, réaffirme l’influence du droit algérien par le droit français en raison de l’absence d’une règlementation spécifique relative au droit de retrait de l’associé. En raison de ce vide juridique, il est nécessaire de se référer aux règles générales du droit civil qui régissent le contrat de société, tout en tenant compte des spécificités des différents types de sociétés commerciales et des textes qui les régissent. Il est à préciser, que le retrait de l’associé peut être volontaire suite à sa renonciation à ses droits sociaux, mais il peut être involontaire dans le cas du retrait judicaire, quand il s’agit de mettre fin de manière unilatérale aux fonctions de l’associé. En règle générale, le retrait de l’associé entraine obligatoirement la dissolution de la société, notamment dans le cas des sociétés de personnes, sauf si les statuts de la société ou les associés ont convenus autrement, c’est à dire de la continuité de la société.
Keywords: Associés; Droit algérien; Droit comparé; Liquidation; Retrait d'associé; Scission; Société; التصفية; الشركاء; الشركة; القانون الجزائري; القانون المقارن; القسمة; انسحاب الشريك

أحكام التنازل عن الحصص وانتقالها في الشركة ذات المسؤولية المحدودة - بشيخ, ام الخير (Ibn Khaldun University of Tiaret, 2023)
المبدأ العام في الشركة ذات المسؤولية المحدودة هو تقييد التنازل عن الحصص، إذ لا يجوز التنازل عن الحصص إلى الغير إلا بموافقة أغلبية الشركاء الحائزين لثلاثة أرباع رأس المال. وهو ما نصت علية المادة571 من القانون التجاري. والاستثناء حرية التنازل عن الحصص إلى الأصول والفروع والأزواج مالم ينص القانون الأساسي على تقييد التنازل. كما يخضع فيها التنازل عن الحصص للاسترداد وهو حق مقرر لمصلحة الشركاء والشركة لشراء الحصص المرغوب في التنازل عنها في حالة رفض الموافقة على المتنازل إليه. وإذا كان الأصل العام في الشركة ذات المسؤولية المحدودة هو تقييد التنازل عن الحصص، فإن الحصص في هذه الشركة تنتقل بكل حرية إلى ورثة الشريك، بشرط أن لا يترتب على ذلك زيادة عدد الشركاء عن الحد الأقصى المقرر قانونا والذي هو 50 شريكا. ومع ذلك يمكن للشركاء تقييد انتقال الحصص إلى الورثة بشرط أن يتم إدراج هذا الشرط في القانون الأساسي للشركة. The general principle in a limited liability company is to restrict the assignment/ abdication of shares, as it is not permissible to assign shares to third parties except with the share-holders majority’s approval who possess three-quarters of the capital. This is what is stipulated in Article 571 of the Commercial Law. The exception is the freedom to assign/transfer shares to ascendants, descendants, and spouses, unless the Basic Law stipulates a restriction of abdication. In addition, the assignment of shares is subject to recovery, which is a right established in the interest of the partners and the company to purchase the desired shares to be assigned in the event of refusal to approve the assignee. Therefore if the general principle in the limited liability company is to restrict the abdication from shares, then the shares in this company are transferred freely to the partner’s heirs, provided that this does not result in an increase in the number of partners beyond the legally prescribed maximum, which are 50 partners. However, the partners can restrict the transfer of shares to the heirs, provided that this condition is included in the articles of association of the company.
Keywords: Associés; Cession d'actions; Droit de rachat; Offre d'actions; Société à responsabilité limitée

La protection des actionnaires minoritaires des sociétés anonymes dans l'espace juridique OHADA - Oueina, Florent (Université de Perpignan Via Domitia, 2023)
Susceptible d'être lésés dans leurs droits représentés par les actions dont ils disposent, les minoritaires dans une société anonyme, ont besoin d'être protégés « non parce qu'ils sont minoritaires, mais parce que leurs intérêts apparaissent comme dignes de protection ». Il n'est pas rare dans le cadre du fonctionnement de la société anonyme d'assister à la prise de décisions contraires, non seulement à l'intérêt des minoritaires, mais également à l'intérêt social, par les actionnaires majoritaires dans l'unique dessein de satisfaire les membres de la majorité au détriment des autres actionnaires. Cette tendance à l'écrasement des minoritaires entraîne des conflits, sinon des oppositions entre actionnaires conduisant à la constitution de blocs antagonistes dont l'attitude peut provoquer une crise au sein de la société. L'étude réside dans l'analyse des garanties et dans la recherche constante d'une protection efficace qu'offrent le législateur et l'autorité du marché financier aux investisseurs minoritaires dans l'espace OHADA. Cette étude étendue en droit français existe aussi en droit OHADA. Likely to be infringed in their rights represented by the actions at their disposal, minority shareholders in a public limited company need to be protected "not because they are in the minority, but because their interests appear to be worthy of protection". It is not uncommon in the context of the operation of the limited company to witness the taking of decisions contrary, not only to the interests of the minority shareholders, but also to the corporate interest, by the majority shareholders in the sole purpose of satisfying the members of the majority to the detriment of the other shareholders. This tendency to crush minorities leads to conflicts, if not oppositions between shareholders leading to the formation of antagonistic blocs whose attitude can provoke a crisis within society. The study lies in the analysis of guarantees and in the constant search for effective protection offered by the legislator and the financial market authority to minority investors in the OHADA area. This extended study in French law also exists in OHADA law.
Keywords: Actionnaire minoritaire; Company profits; Droit OHADA; Droit français; Droit à l'information; Intérêt social; Marché financier OHADA; Minority shareholder; OHADA Law and French Law; OHADA stock market; Public limited companies; Rights of information; S.A.; Société Anonyme

Liability in the atmosphere of groups of companies - Motassim, Sofia (Universitat de Barcelona, 2023)
Groups of companies are a complex corporate structure, whose regulation can be problematic, especially when it comes to liability. Indeed, liability within corporate groups draws forth a series of issues principally due to the principles of separate corporate personality and limited liability. In the context of limited liability, which is based on the notion of separate legal personality, the main issue waxes the protection of the creditors, in particular the creditors of the subsidiaries. One can find three regulatory templates for handling corporate groups and their liability: policing via general company and/or civil law (such as the English model); policing via special group legislation (such as the German model); and policing via branches of law such as insolvency law, antitrust law, and contract law, among others (which is the case in numerous jurisdictions, either coupled with the first or the second model). Lifting the corporate veil has come as an answer to corporate separateness, by permitting to ignore the shareholders’ limited liability and hold them personally liable for the debts of their companies in specific circumstances. However, one can hardly find cases in which the corporate veil has been successfully lifted, due to many factors. Other important questions that are posed in the scope of corporate groups liability are the parent company’s liability for the payment of its daughter companies’ debts when insolvency strikes and other respects, besides the matter of group liability. Furthermore, liability is as well a key player in terms of tort law, and corporate social responsibility has therefore found a place in the sun in the present climate.
Keywords: Ciències Jurídiques; Commercial law; Conglomerate corporations; Corporations; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Grupos de empresas; Grups d'empreses; Liability (Law); Responsabilidad (Derecho); Responsabilitat (Dret); Sociedades; Societats

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

The Double Life of State-Owned Enterprises in International Economic Law: States, Corporations or Both? - Kikarea, Eirini (University of Cambridge, 2023)
State-owned enterprises (SOEs) have recently gained prominence in global markets and feature among the world’s most influential enterprises. The aim of this research project is to analyse the international norms in force regulating whether SOEs are considered state or non- state actors, and their conduct state or non-state conduct, the interpretation and application of these norms by adjudicators in different international regimes, and to provide alternative prisms through which these rules and decisions can be assessed and re-thought by political actors. I show that, in relation to SOEs, the concepts ‘state and ‘act of state’ have been ascribed diverse meanings by adjudicators and other international actors, who have employed legal standards with divergent wording and thresholds when dealing with similar questions. I argue that the fragmented meaning of these terms should be understood, in part, as a result of the inherent malleability of these terms and the different expert vocabularies employed across regimes. It is exhibited that adjudicators in the international trade and investment regimes are more inclined towards piercing the corporate veil of SOEs, potentially evidencing the existence of biases against SOEs, which are perceived as inherently economically inefficient and politically motivated actors in an indiscriminatory manner. In the last chapter, I introduce alternative lines of thought regarding the regulation of SOEs in international law. I suggest that, instead of engaging in theoretical discussions on the proper delineation between the public and the private sector, it is more useful to focus on the distributional impact of international rules on various actors, especially on developing and emerging economies where the presence of SOEs is very high. Such alternative prisms of analysis open paths for future research and practice, with the goal of designing an international economic order that incentivises institutional experimentation in the pursuit of economic development and distributional equity.
Keywords: International Economic Law; International Investment Law; International law; International trade law; Public enterprises; State capitalism; State-owned enterprises

La protection des associés minoritaires : étude comparée de droit français et droit OHADA - Moundounga Mapangou, Ulrich (Université de Pau et des Pays de l'Adour, 2023)
La protection juridique des associés minoritaires se justifie en droit des sociétés et en droit OHADA par l’absence directe de la gestion des sociétés commerciales par ces derniers. De ce fait, les deux ordres juridiques mettent en œuvre plusieurs mécanismes afin de protéger les intérêts des minoritaires. Ces mécanismes sont de plusieurs natures à savoir des règles juridiques favorisant un traitement égalitaire de tous les associés ou des droits exclusifs aux associés minoritaires favorisant un équilibre de pouvoirs dans la gestion de la société mais également la coexistence d’acteurs capables de réguler le bon fonctionnement de la société, notamment le juge, les associations de défenses d’intérêts des associés minoritaires.Dans les sociétés où les enjeux économiques sont très importants comme les sociétés faisant appel public à l’épargne, les législateurs français et OHADA, soucieux de protéger les associés minoritaires, ajoutent au droit commun, l’intervention du droit des marchés financiers qui vient renforcer la protection des minoritaires, notamment dans l’exercice de leur droit de cession. Ainsi, l’on remarque que le droit des sociétés français et le droit OHADA utilisent quasiment les mêmes fondements juridiques pour protéger les associés minoritaires. Il existe plus de similitudes que des différences dans les deux ordres juridiques puis que le législateurs OHADA a entrepris une réforme en 2014 afin de renforcer considérablement les compétences des associés minoritaires dans la gestion de la société. Cette réforme du droit OHADA s’est quasiment rapprochée du droit de société.Toutefois, malgré les efforts du droit des sociétés français et du droit OHADA de protéger les intérêts des associés minoritaires, subsiste une précarité du statut des minoritaires. La loi de la majorité fait obstacle à ce que l’on puisse objectiver que la protection apportée aux associés minoritaires est absolument efficace. Pour en arriver à une protection efficace certains droits devraient être généralisés pour contrôler sereinement la gestion sociale et leurs intérêts. The legal protection of minority shareholders is justified in company law and in OHADA law by the direct absence of management of commercial companies by the latter. As a result, both legal systems implement several mechanisms to protect the interests of minority shareholders. These mechanisms are of several kinds, i.e. legal rules favouring equal treatment of all partners or exclusive rights for minority partners favouring a balance of power in the management of the company, but also the coexistence of actors capable of regulating the proper functioning of the company, in particular the judge, and associations defending the interests of minority partners.In companies where the economic stakes are very high, such as companies making public offerings, the French and OHADA legislators, anxious to protect minority shareholders, add to common law the intervention of financial market law, which reinforces the protection of minority shareholders, particularly in the exercise of their right to sell. Thus, it can be seen that French company law and OHADA law use almost the same legal basis to protect minority shareholders. There are more similarities than differences in the two legal orders since the OHADA legislators undertook a reform in 2014 in order to considerably strengthen the powers of minority shareholders in the management of the company. This reform of OHADA law has almost come close to company law.However, despite the efforts of French company law and OHADA law to protect the interests of minority shareholders, the status of minority shareholders remains precarious. The law of the majority prevents the protection of minority shareholders from being absolutely effective. To achieve effective protection, certain rights should be generalised in order to control the management of the company and their interests.
Keywords: Associé; Corporate law; Droit des sociétés; Droit des sociétés commerciales; Droits des associés; French law; Minoritaire; Minority; OHADA law; Ohada; Organisation pour l'harmonisation en Afrique du droit des affaires; Protection; Shareholders

The regulation of Corporate phoenix activity in South Africa - Basson, André Stephan (University of Johannesburg, 2023)
Phoenix activity involves conduct whereby a failing company (the old company) is replaced by a second company (the new company) in the operation of the same or a similar business and that involves the same or similar company controllers. Transactions of this nature can be legal and even be beneficial to society, since entrepreneurs who pursue a viable business may, if the new company succeeds, benefit the economy and many other stakeholders. These transactions are referred to as legal phoenix activity. Problems arise however when phoenix activity is engaged in with the goal of evading the debt of the old company, known as illegal phoenix activity. In other cases, even well-intentioned company controllers can cause significant harm by resurrecting a fundamentally flawed business. This conduct, although not illegal, is unduly prejudicial to stakeholders and is known as problematic phoenix activity. While this thesis focuses on illegal phoenix activity, several measures identified should also curb problematic phoenix activity. This study identifies the elements and common characteristics of illegal phoenix activity. It then analyses regulation pertaining to those elements and common characteristics with the aim of finding effective solutions to the problem. This includes evaluating measures that reverse prejudicial transactions that occur during illegal phoenix activity as well as holding complicit parties, such as company controllers and the new company, accountable for their actions. Regulation aimed at preventing and investigating illegal phoenix activity is also considered. This thesis uses the comparative legal approach to analyse regulatory responses to illegal phoenix activity. Australia, the United Kingdom, and the United States of America are examined. Several reported cases in South Africa involving what appear to be illegal phoenix activity are explored, along with the existing measures that are applicable to illegal phoenix activity in South Africa. A single anti-phoenix provision is undesirable as it has the potential to unjustifiably infringe on legal phoenix activity. This thesis proposes a multi-pronged approach, which involves a combination of better enforcement of existing laws and the introduction of smaller targeted amendments to legislation aimed at reducing the incidence illegal phoenix activity.
Keywords: ABUSE OF THE CORPORATE FORM; Bankruptcy fraud; Evasion of liability; Fraud on creditors; Phoenix activity; Phoenixism; Strategic bankruptcy; Successor liability; Transactions prejudicing creditors; Transfers at an undervalue

Kurumsal yönetim bakış açısıyla mali durumu bozulan anonim şirketlerde alacaklıların menfaatinin korunması - Demi̇rel Özdemi̇r, Duygu (Kocaeli Üniversitesi, 2023)
Anonim şirketler hukukunda alacaklılar, şirketlerin dış finansman kaynaklarının merkezini oluşturmakta ve bu nedenle de son derece önemli bir menfaat grubunu teşkil etmektedirler. Bu durum şirket alacaklılarının çıkarlarının etkin bir biçimde gözetilmesi ve korunmasını gerekli kılmaktadır. Zira alacaklıların alacaklarına kavuşabilmeleri için müracaat edebilecekleri tek kaynak şirketin malvarlığıdır. Dolayısıyla anonim şirketin mali durumunun bozulması sonucu malvarlığının kayba uğraması veya uğrama tehlikesi altında olması, alacaklıların menfaatlerini zedeleyici niteliktedir. Bu durum mali durumu bozulan anonim şirketlerde, alacaklıların menfaatlerinin gözetilmesini ve özellikle de öncül (ex-ante) koruma imkânlarıyla bu risk gerçekleşmeden önce bu konuda tedbirler alınmasını gerektirmektedir. Kurumsal yönetim anlayışı, anonim şirketlerde menfaat grupları arasındaki çıkar çatışmalarının en iyi, en adil şekilde dengelenmesini hedeflemektedir. Bu itibarla bu tez çalışmasında söz konusu menfaat çatışmaları özelinde kurumsal yönetimin şeffaflık, adillik, hesap verilebilirlik ve sorumluluk ilkeleri çerçevesinde bir menfaat grubu olarak şirket alacaklılarının menfaatlerinin, mali durumu bozulan veya bozulma tehlikesi altında olan anonim şirketlerde nasıl gözetilmesi ve korunması gerektiği hususunda bir bakış açısı sunulması hedeflenmektedir. Bu bakış açısından hareketle sermaye kaybı yaşayan, borca batık hale gelen anonim şirketlerin mali durumlarının iyileştirilmesi maksadıyla sermayenin korunması esası benimsenerek öngörülen TTK m.376 hükmü ile bu hükmün uygulanmasına ilişkin Tebliğ kapsamında öngörülen düzenlemelerin, alacaklıların menfaatlerinin korunması bakımından etkileri tartışılmaktadır. Ayrıca ilgili hükümlerin, şirketlerin mali yapılarının güçlendirilmesi bakımından yeterlilikleri ve yerindelikleri, karşılaştırmalı hukuk düzenlemeleri de göz önünde bulundurularak eleştirel bir bakış açıyla ayrıntılı şekilde incelenmektedir. Creditors are the key to external financing sources for companies under the statute of joint stock companies, and hence represent an important figure interest group. This situation needs the effective supervision and protection of the company's creditors' interests. This is because the company's assets are the only source to which creditors can turn to acquire receivables. Hence, the loss or threatened loss of the joint stock company's assets because of its worsening financial situation is detrimental to the creditors' interests. This circumstance necessitates that the interests of the creditors of companies with a worsening financial situation be considered and that steps be taken in this respect prior to the realization of this danger, particularly with ex-ante protection opportunities. The corporate governance method strives to achieve the most equitable resolution of conflicts of interest between interest groups in joint stock companies. This thesis aims to provide a perspective on how the interests of company creditors, as an interest group, should be observed and protected in joint stock companies whose financial situation deteriorates or is at risk of deterioration, within the framework of the principles of transparency, fairness, accountability, and responsibility of corporate governance. From this perspective, to improve the financial situation of companies that have capital loss and become over-indebted, the effects of the provisions of TCC art.376 and the Communiqué, which are envisioned based on the principle of capital maintenance, are discussed in terms of protecting the interests of creditors. In addition, the adequacy and suitability of the relevant rules in terms of strengthening the financial structures of corporations are analysed in depth from a critical standpoint, considering the norms of comparative law.
Keywords: Corporate governance; Creditors; Financial distress; Joint stock company

Anonim şirketlerde imtiyazlı paylar - Erten, Cengiz (Kocaeli Üniversitesi, 2023)
6102 sayılı Türk Ticaret Kanunu (TTK) ile Türk Ticaret Hukuku'nda özellikle anonim şirketler hukukunda yapılan değişiklikler arasında imtiyazlı paylarla ilgili düzenlemeler de bulunmaktadır. Mülga 6762 sayılı Türk Ticaret Kanunundaki (eTK) hükümlere benzerlik gösteren yönleri olsa da imtiyazlı paylarla ilgili daha ayrıntılı, yenilikler getiren ve önceki Kanun döneminde karşılaşılan sorunları gidermeye çalışan düzenlemelerin yapıldığı görülmektedir. TTK'daki imtiyazlı paylarla ilgili düzenlemelerin eTK döneminde ortaya çıkan sorunları giderip gidermediğinin ya da yeni sorunlara, belirsizliklere ve tartışmalara yol açıp açmadığının tespit edilerek değerlendirilmesi amacı bu tezin yazılmasına sebep oluşturmaktadır. Birinci bölümde önce genel olarak pay kavramı, imtiyazlı payın tanınması koşulları, imtiyaz kavramının terminolojik yönü ve mevzuatımızda konuyla ilgili düzenlemelerle hukuk sistemimize esin kaynağı olan yabancı hukuk sistemlerindeki düzenlemeler incelenmiştir. Ardından, imtiyaz tanınan hakların, eşitlik ilkesi, müktesep hak ve vazgeçilmez hak ile olan ilişkilerine değinilmiş ve imtiyazlı pay kavramının nasıl tanımlanması gerektiği üzerinde durulmuştur. Tezin asıl omurgasını oluşturan ikinci bölümde, imtiyaza konu haklar, malvarlığı hakları ve yönetim hakları olarak iki asıl eksen üzerinde incelenmiştir. İkinci bölüm için en fazla tartışılmış bulunan konu, yönetim haklarında imtiyaza ilişkindir. Yönetim haklarında imtiyazı oluşturan iki alt başlık, oy hakkında imtiyaz ve yönetim kurulunda temsilde imtiyaz ayrıntılı bir şekilde incelenmeye çalışılmış, imtiyazın kanundan kaynaklanan nedenlerle engellenmesinden bahsedilmiş ve diğer haklarda imtiyaza değinilmiştir. Tezin üçüncü bölümü imtiyazların korunması konusuna ayrılmıştır. Bu bölümde imtiyazlı pay sahipleri özel kurulunun (İPSÖK) yapısı, niteliği ve toplanması ile özel kurulun onayına bağlı kararlar halka açık olan ve olmayan şirketler dikkate alınarak açıklanmıştır. Üçüncü bölümde ayrıca İPSÖK kararlarına karşı açılacak iptal davalarıyla ilgili değerlendirmeler yapılmıştır. It is observed that although there are some similarities with the previous one, the new Turkish Commercial Code, Law No: 6102, introduces more detailed and innovative arrangements which is intended to provide an answer to the problems experienced during the abrogated code was in force in relation to preference shares. It is easily can be said that, by and large, the topic "preference shares" is the one of the most radically altered topic in the new code. The main purpose of this thesis is to shed light whether these innovative arrangements in the new code actually solving the problems that is intended to solve or, rather opposite, causing new problems and ambiguities. For this purpose, the first section of this thesis is allocated to analyse the concept of "share" in general and under which conditions the preference shares are granted first and then the meaning of the concept of "preference" is investigated. It is followed by subsections devised to identify the current domestic law, and comprative law that inspried the law makers in this area. In the following subsections it is attempted to explain where preference shares stand with respect to principle of equality, vested interests and inalienable rights, and how the concept of preference shares should be defined. In the second section, which constitutes the backbone of this thesis, the rights that are being subject of the preference shares are examined on the axis of the assest rights and the administrative rights. The topic of the administrative rights attached to preference shares is the most debated topic in this section. In this context under the head of the administrative rights, the issues related to priveleges in votes and the representation on the executive board are examined seperately in two separate subsections. Also in this subsection the issues of statutory basis of the prevention of preferences and the preferences in relation to other rights are grappled. The third section of the thesis is completely devised to the issues related to the protection of the preference shares. In this section the structure, qualifications, gathering of the board of preference shares owners and the decisions subject to approval of this board are explained in the context of private and public companies. In this section the suits that could be brought for the annulment of this board decision is evaluated briefly.
Keywords: Joint stock company; Preference Shares

Anonim ortaklıkta yönetim ve temsil yetkisinin devrinde yönetim kurulu üyelerinin hukuki sorumluluğu - Kalender, Süleyman (Çukurova Üniversitesi, 2023)
Anonim şirketlerde yönetim veya temsil yetkisi kural olarak yönetim kurulu tarafından kullanılmakla birlikte, özellikle halka açık veya büyük ölçekli ortaklıklarda söz konusu yetkilerin tamamının yönetim kurulu tarafından bizzat yerine getirilmesi uygulamada sık rastlanan bir durum değildir. Bu nedenle kanunda, yönetim kuruluna, yönetim veya temsil yetkisinin 6102 sayılı Türk Ticaret Kanunu' nun 367/I ve 370/II hükümlerinde yer alan şartlara uygun olarak, mevcut yönetim kurulu üyelerinden bir veya birkaçına yahut üçüncü kişilere devretmek suretiyle, şirketin yönetim teşkilatını belirleme yetkisi tanınmıştır. Şirket yönetimi konusunda uzmanlaşmış ve yeterli mesleki tecrübeye sahip olan kişilere yetkilerin devredilmesi, bir yandan şirkette profesyonelleşmeyi sağlamakta, diğer yandan kural olarak, devredilen yetkilerle birlikte bu kapsamda ortaya çıkabilecek hukuki sorumluluk da devredilmiş sayılacağından, yönetim kurulu üyelerinin hukuki sorumluluğunu sınırlandırmaktadır. Yönetim veya temsil yetkilerinin geçerli bir şekilde devredilmesi halinde, devredilen yetkilerle ilgili olarak yönetim kurulu üyelerinin hukuki sorumluluğu; murahhasların seçiminde, onlara verilecek talimatlarda ve murahhasların üst gözetiminde göstermeleri gereken makul derecede özen yükümlülüğü ile sınırlı olarak devam eder. Çalışmamızda, geçerli ve geçersiz yetki devri hallerinde, yönetim kurulu üyelerinin hukuki sorumluluğunun ne şekilde ortaya çıkacağı meselesi, mehaz İsviçre hukukundaki görüş ve yargı kararlarına yer verilmek suretiyle, detaylı bir şekilde incelenmiştir. Although the management or representation authority in joint stock companies is used by the board of directors as a rule, it is not common in practice that all of the said authorities are personally exercised by the board of directors, especially in publicly held or large-scale partnerships. For this reason, in the law, the board of directors is authorized to determine the management organization of the company by delegating the management or representation authority to one or more of the existing board members or to third parties in accordance with the provisions of the Turkish Commercial Code numbered 6102, 367/I and 370/II has been recognized. Delegation of powers to people who are specialized in company management and have sufficient professional experience, on the one hand, ensures professionalization in the company, and on the other hand, as a rule, legal responsibility that may arise in this context together with the delegated powers will be deemed to have been transferred, thus limiting the legal liability of the members of the board of directors. In case of a valid transfer of management or representation powers, the legal responsibility of the members of the board of directors regarding the delegated powers; limited to the reasonable care obligation that they must show in the selection of the executive directors, in the instructions to be given to them and under the supervision of the executive directors. In our study, the issue of how the legal responsibility of the members of the board of directors will arise in cases of valid and invalid delegation of authority has been examined in detail by including the opinions and judicial decisions in the Swiss law.
Keywords: Board of directors; Joint stock company

Corporate Governance and Women on the Board of Directors : the Legal Framework towards a Minimum Harmonisation in the European Union - Lamy Martin, Joy (Université Paris-Saclay, 2022)
This thesis concerns the recent and considerable change in corporate governance legislation, specifically how boards of directors address the issue of parity and the appointment of its members in public limited companies. This research will challenge European Union law which, to date, does not propose EU harmonization.The UK, France, Germany and Norway (a non-member country but one that will be included in this research) have introduced changes to their national legislation in relation to company boards in public listed companies. This research will focus on a comparative study of parity on company boards under European Union law and its application in the UK (pre-Brexit), Germany, France and Norway. The application of corporate governance codes or soft law and the proposal for a hard law directive demonstrate a fragmentation in the EU, as the application of law by hard quotas divides member states and parliamentarians in European Union law. Corporate governance law in the member states varies considerably, but it must respect the EU's primacy law. Comparisons of legislation between member states reveal the marked differences in law.Women are significantly under-represented on the corporate boards of public limited companies in Europe. Legitimate questions need to be asked. Does the European Commission have the right to make a proposal for a directive allowing for parity on the boards of public limited companies in the EU? The reality is that the Commission does not have a solid approach in dealing with the issue of parity. As long as there is too much inconsistency between Member States, this leaves considerable room for further research. Legislation and governance law between member EU member states diverge considerably and demonstrate inconsistency with the legislation between them, resulting in little or no consensus in the interpretation of EU law. Or member states diverge with opposing interpretations of EU law, especially concerning sovereignty.National legal systems differ considerably in the way legislation allows for the appointment of board members and the notion of parity. A review of corporate governance matters concerning shareholders, the composition and appointment of board members corporate governance codes reveal the gap between member states. The research focus on parity by way of a comparison of the soft and hard laws of the member states.. The research upholds European law Article 157(3) Treaty of the Functioning on the European Union (TFEU), which is the fundamental principle of EU law and basis of gender equality and parity.The research will contribute to raising awareness of this issue through quota legislation and the question of parity on boards in public limited companies in the EU.
Keywords: Board of directors; Comparative Law; Conseil d'administration; Corporate Governance; Droit comparé; Gender and parity; Genre et parité; Gouvernance des entreprises; Quotas; The European Union; Union européenne

Les conflits d'intérêts en droit des sociétés - Boucant, Nicolas (Université Paris 12, 2022)
De sa création jusqu’à son terme, la société peut faire face à des interférences entre ses intérêts, d’une part, et les intérêts des associés, des dirigeants et des personnes auxquelles ils sont liés, d’autre part. En droit des sociétés, la genèse des conflits d’intérêts réside dans la volonté des associés et des dirigeants de privilégier leurs intérêts ou ceux d’une personne à laquelle ils sont liés, au détriment de l’intérêt social. Cette recherche a pour objectif de proposer une grille de lecture juridique renouvelée de la notion de conflit d’intérêts, articulée autour du préjudice et du devoir de loyauté. Elle met en évidence une méthodologie afin de définir le conflit d’intérêts en droit des sociétés. La présente étude identifie avec précision les mécanismes pratiques de détection, de prévention, de gestion, de sanction et de réparation des conflits d’intérêts.
Keywords: Company; Conflicts of interests; Conflits d’intérêts; Corporate law; Damage; Droit des sociétés; Interests; Intérêt social; Intérêts; Loyalty; Loyauté; Pouvoir; Power; Préjudice; Règlement de conflits; Sociétés

La régulation des entreprises multinationales en Afrique subsaharienne : De l'instrumentalisation à la prise en compte d'un développement collectif durable par les stratégies RSE (Responsabilité Sociale de l'Entreprise) - Monemou, Adama Esperance (Université de Toulon, 2022)
Du fait de son pouvoir de régulation, la Responsabilité Sociale de l’Entreprise (RSE) est foncièrement un instrument au service du développement durable. Ainsi, l’émergence et la diffusion de cet instrument en Afrique subsaharienne doit répondre à plusieurs besoins, au premier rang desquels figurent la réalisation des Objectifs du Développement Durable (ODD) et la contribution à l’atteinte des Objectifs du Millénaire pour le Développement (OMD). C’est dans cette perspective que les entreprises multinationales trouvent leur place et sont visées par le champ normatif de la RSE. Le questionnement éthique et social des entreprises multinationales en Afrique subsaharienne conduit inéluctablement à rechercher différents leviers de régulation sous les trois (3) aspects, à savoir environnemental, social et économique, pour la mise en œuvre opérationnelle de la RSE. Sans occulter le foisonnement d’initiatives RSE, y compris les démarches volontaires des entreprises multinationales souvent matérialisées par les codes de conduite, un système de régulation contraignant semble se configurer à l’échelle internationale sous l’impulsion des organisations internationales, la pression des ONG et des parties prenantes dont les investisseurs. Par conséquent, les entreprises multinationales, soucieuses de préserver leur image, leur légitimité ainsi que l’ancrage dans les territoires d’implantation, doivent garantir la transparence et la cohérence des pratiques, face au manque d’effectivité souvent constaté des discours RSE qui ne répondent qu’aux finalités marketing et commerciale. Cette instrumentalisation justifie l’immixtion du droit et la construction progressive d’un véritable droit de la RSE, avec une approche à la fois réglementaire tendant à favoriser la production de normes à caractère contraignant, du moins exemptes de toute instrumentalisation et stratégique en procurant un avantage compétitif aux entreprises engagées en RSE par la voie de la consommation responsable et pour que celles-ci apportent une contribution au développement collectif durable des territoires d’implantation.
Keywords: Afrique subsaharienne; Corporate Social Responsibility; Droits de l'homme; Développement durable; Entreprises multinationales; Human rights; Instrumentalisation; Instrumentalization; Millenium development goals; Multinational companies; Objectifs du développement durable; Objectifs du millénaire pour le développement; Regulation; Responsabilité sociale de l'entreprise; Responsabilité sociétale des entreprises multinationales; Régulation; Sub-Saharan Africa; Sustainable development goals

A interdisciplinaridade do Direito Societário e do Direito Tributário: da desvinculação do balanço societário para fins tributários. O lucro contábil das concessionárias de serviços públicos de transmissão de energia elétrica - Ippolito, Marcelo Baeta (Universidade de São Paulo, 2022)
O tema que envolve as diferenças entre o lucro contábil para fins societários e para fins tributários é sempre polêmico, ainda que o lucro, para fins societários, no Brasil, seja utilizado como ponto de partida para a determinação da base de cálculo do imposto sobre a renda das pessoas jurídicas. Nesta tese, entretanto, estas diferenças serão abordadas sob ângulos diferentes e com base em situações contemporâneas e pragmáticas que expõem, com maior profundidade e clareza, as razões e fundamentos delas, de modo que, a despeito da reconhecida contribuição da interdisciplinaridade envolvendo o direito societário e a contabilidade e, por outro lado, o direito societário e o direito tributário, tendo como objeto de conhecimento o referido lucro contábil, será possível, especialmente por conta das novas dificuldades trazidas pela introdução do novo padrão contábil no Brasil, provar a conveniência e a necessidade da desvinculação do lucro contábil e suas respectivas regras de apuração, nos termos da legislação societária, para efeito de consideração como ponto de partida, de acordo com as regras atuais, para apuração da base de cálculo do imposto sobre a renda das pessoas jurídicas. Nesse sentido, inicialmente, o caminho a ser trilhado no presente trabalho de pesquisa e desenvolvimento da tese de doutorado é determinado pela consideração do direito como objeto cultural, criado pelo homem e, como tal, para ser conhecido e apreendido, necessário se faz a sua expressão em linguagem. Por outro lado, importante abordagem do tema levará em consideração que há independência da linguagem em relação à realidade, bem como que a mesma linguagem constitui a realidade conceptual que, por sua vez, é a única passível de ser objeto de conhecimento. Portanto, é possível afirmar que uma das contribuições originais da tese corresponde a essa abordagem do lucro como uma realidade conceptual, constituída pela linguagem contábil, na medida em que será capaz de fornecer maiores subsídios e elementos para melhor se mensurar as dificuldades do compartilhamento desse objeto de conhecimento pelo direito societário e tributário, promovido pela interdisciplinaridade desses ramos do direito, especialmente quando a realidade conceptual que atende aos interesses específicos do direito societário se distanciou enormemente da realidade conceptual que se quer regular por meio do direito tributário, tendo em vista a aplicação de novas normas sintáticas, semânticas e pragmáticas da linguagem contábil. Para efeito de se demonstrar o distanciamento das realidades conceptuais correspondentes aos objetos de conhecimento do direito societário e tributário, a utilização das demonstrações financeiras das Concessionárias de Serviços Públicos de Transmissão de Energia Elétrica como parâmetro traz, também, originalidade à tese, correspondendo à prova efetiva de como a utilização do lucro contábil societário, também para fins tributários, pode gerar mais dificuldades para ambas as áreas do direito do que contribuições positivas.
Keywords: Accounting; Concessionaires; Concessionárias; Contabilidade; Interdisciplinaridade; Interdisciplinarity; Lucro; Profit; Public Utilities; Serviços Públicos

Le quasi associé en Droit OHADA et Droit Français - Aquereburu, Edouard-Robert (Université Paris 12, 2022)
Ce travail ambitionne d’étudier des notions ayant des droits et un régime proche de celui de l’associé mais auquel le droit ne reconnaît pas la qualité d’associé. Jusqu’ici, la doctrine s’est contentée de définir, de distinguer l’associé de celui qui ne l’était pas. En effet, les auteurs à partir des critères de qualification de l’associé refusent la qualité d’associé au porteur dans le cadre d’une convention de portage. Il existe un débat doctrinal nourri par d'autres auteurs autour de la qualification d’associé de l’usufruitier. A cette idée, rejoignent des fondements textuels qui refusent également, la qualité d’associé aux titulaires de valeurs mobilières donnant accès au capital ainsi qu’aux fiduciaires.Aussi ce travail a pour intérêt de démontrer qu’il existe un cadre commun à plusieurs de ces concepts juridiques existant autour de la notion d’associé au sein du droit français et au sein de l’espace régit par le droit OHADA. La notion de quasi-associé a été encore peu interrogée aussi bien en droit Français qu’en droit OHADA. Largement inspiré du droit français, le droit OHADA recèle quelques particularités en raison du contexte et de la coutume africaine. Ce travail comparatif entre le droit Français et le droit OHADA relèvera les singularités existantes au sein du droit OHADA sur la notion de quasi associé.Deux approches méthodologiques sont mobilisées pour étudier le quasi-associé au sein du droit des sociétés français et de l’espace OHADA.La première approche est de comparer les critères de qualification de l’associé aux concepts juridiques retenus. La seconde approche est de s’appuyer sur les outils jurisprudentiels, textuels et la doctrine afin d’identifier d’autres critères.les concepts juridiques sélectionnés agissent comme étant des associés sans pour autant recevoir la qualification d’associé.Enfin, le travail aura pour objectif final d’identifier les conditions et le régime pour ce quasi-associé. Bref, définir ce qu’est un quasi-associé à la lumière du droit français et du droit OHADA.
Keywords: Associé; Capital investissement; Corporate law; Droit des sociétés; Informal society; Ohada; Partner; Private equity; Securities; Société informel; Valeurs mobilières

La vertiente societaria del contrato de gestión hotelera - Moguel Fernández, Jordi (Universitat de Lleida, 2022)
En aquest treball s’examina, amb l’ajuda d’un estudi de casos múltiples, la naturalesa societària que adquireix aquell contracte de gestió hotelera en què el prestador de serveis és una cadena que implanta el seu model d’empresa en una xarxa d’allotjaments a la qual s’incorpora l’establiment objecte d’aquella relació jurídica. En aquest marc, la perfecció de la modalitat contractual esmentada no només comporta que el gestor de l’allotjament hagi de vetllar pels interessos aliens, sinó també que hagi de salvaguardar i executar les regles que beneficien el conjunt d’explotacions hoteleres que comparteixen uns mateixos intangibles. És en aquest darrer àmbit on sorgeix el “grup de negocis” com una organització de caràcter jeràrquic que pot englobar-se en l’ampli fenomen dels grups de societats, la missió del qual és promoure el prestigi i l’òptim funcionament de la xarxa hotelera per a després traslladar tals beneficis als diferents allotjaments que s’incorporen a l’agrupació mitjançant contractes com el de gestió hotelera. Així mateix, dintre d’aquesta estructura grupal es mantenen relacions associatives entre els seus integrants, cosa que dona lloc a una societat interna en la qual els seus socis assumeixen el compromís de respectar i complir els estàndards de la cadena, així com els serveis grupals que aquesta estableixi amb tal propòsit. Aquesta tesi analitza en profunditat l’esmentada arquitectura jurídicosocietària des de la perspectiva del dret mercantil, prestant atenció principalment al dret de societats i al de la competència, sense deixar de costat el dret d’obligacions i contractes. A més, s’estudien amb deteniment els diferents conflictes intragrup que poden derivar-se de les vicissituds d’aquella complexa estructura organitzativa, davant dels quals es proposen diversos remeis jurídics a partir de solucions que ofereix el dret espanyol.
Keywords: Conflictes intragrup; Conflictos intragrupo; Contracte de gestió hotelera; Contrat de gestion; Contrato de gestión hotelera; Dret Mercantil; Gestion hôtelière; Group of companies; Grup de societats; Grupo de sociedades; Hotel management agreement; Hôtel; Intragroup conflicts

L'éviction des associés d'une société en difficulté - Thiéry, Emilie (Université Paris 1, 2022)
Le traitement des associés d’une société en difficulté repose sur l’application cumulative du droit des sociétés et du droit des procédures collectives. Cette cohabitation, sans tentative de synchronisation, ne résiste pas au test de cohérence entre le droit des procédures collectives, qui aménage les droits patrimoniaux des associés, et le droit des sociétés, qui maintient par principe leurs droits extra-patrimoniaux. Cette situation conduit à conférer aux associés, pourtant titulaire d’une créance de dernier rang, un droit de blocage d’un plan de reprise interne alors que les créanciers sont tenus de consentir des sacrifices. La présente étude a pour objet de trouver une ligne de démarcation entre opposition légitime des associés pour préserver leurs droits et leur nécessaire éviction dans le cadre de l’adoption du plan de reprise interne. La clé de voûte de la réconciliation du droit des sociétés et du droit des procédures collectives, quant au sort des associés d’une société en difficulté, est leur engagement commun de contribuer aux pertes. Cette analyse renouvelée autour de la créance de dernier rang de l’associé implique que toutes les parties affectées, dont les associés, votent les mesures de reprise interne proposées, réunies au sein de classes partageant des caractéristiques homogènes. Ces nouveaux outils consacrés, selon une cohérence retrouvée, permettront de dynamiser les plans reposant sur la reprise interne de la société.
Keywords: Actionnaires; Associés; Company law; Corporate law; Droit des procédures collectives; Droit des sociétés; Entreprises en difficulté; Eviction; Insolvency law; Relations avec les actionnaires; Shareholders

Interpretação do contrato social e do estatuto social no direito societário - Portugal, Daniel Ochsendorf (Universidade de São Paulo, 2022)
Não se deve dizer que o controlador ou que a maioria seria o intérprete do interesse social. Qualquer um, em princípio, pode interpretar o contrato social ou o estatuto social - se o intérprete está certo ou não, isto é outra questão -, e os controladores também podem vir a violar o contrato de sociedade. O contratualismo pode ser associado a algo que dá importância para o contrato social ou para o estatuto social enquanto o institucionalismo pode ser associado a algo que não dá relevância para o contrato social ou para o estatuto social e que, supostamente, se preocupa apenas com o interesse público. Parte do problema do institucionalismo é que o negócio de sociedade termina por ser de algum modo enaltecido exageradamente. As sociedades, certamente, têm um impacto muito forte nas vidas das pessoas em geral, porém os aspectos negociais das sociedades não devem ser deixados de lado - eles são a origem das sociedades
Keywords: Articles of incorporation and bylaws; Contrato social e estatuto social; Corporate law; Direito das sociedades; End of corporations and interests of corporations; Estado de Direito; Fim social e interesse social; Interpretation; Interpretação; Interprétation; Rule of Law; Règlement; Société; Statuts

A desconsideração da personalidade jurídica e os sócios não gestores da sociedade limitada - Ferraz, Fábio Garcia Leal (Universidade de São Paulo, 2022)
A tese objetiva estudar os impactos do instituto da desconsideração da personalidade jurídica aos sócios não gestores da sociedade limitada, após a recente redação da Lei da Liberdade Econômica, que positivou, entre outras situações, o benefício como critério de responsabilização. Dividido em três partes e se valendo da metodologia analítica dedutiva e indutiva, o presente trabalho aborda, no primeiro capítulo, a responsabilidade pelos atos da sociedade limitada, utilizando como base obras importantes, como as de Calogero Gangi, Federico de Castro y Bravo, José Waldecy Lucena, Itamar Gaino e Júlio César Lorens. O capítulo intermediário trata do instituto da desconsideração propriamente dito, trazendo um esboço histórico, alterações legislativas, requisitos de aplicação e direito comparado, se valendo das principais obras sobre o assunto, como as de Rolf Serick, Piero Verrucoli, Rubens Requião e José Lamartine Corrêa de Oliveira, entre outras. No capítulo final, adentra-se a temática central, com o estudo aprofundado do nível de responsabilização dos sócios não gestores quando instaurado o incidente de desconsideração da sociedade limitada (responsabilização subjetiva). Viu-se no estudo que a positivação do critério do benefício não foi uma escolha isenta de críticas, apesar de se tratar de um avanço. No entanto, os sócios não gestores continuam expostos a uma possível responsabilização ilimitada juntamente com os demais sócios gestores e infratores quando aplicada a desconsideração. Ao final do estudo, sugere-se um novo caminho, com uma cláusula híbrida de responsabilização dos sócios, na esperança de contribuir e aprofundar a matéria, pois o impacto gerado pelo instituto aos sócios não gestores é muito pouco explorado, apesar da importância desse tipo de sócio para o investimento passivo nas sociedades brasileiras.
Keywords: Accountability; Associé; Benefit; Benefício; Desconsideração da personalidade jurídica; Disregard of legal entity; Economic Freedom Law; Lei da Liberdade Econômica; Limited company; Non-managing partners; Nongérant; Responsabilização; Sociedade limitada; Société à responsabilité limitée; Sócios não gestores

Mineur et société de famille - Dasque, Marie (Université de Pau et des Pays de l'Adour, 2022)
En tant que personne vulnérable, le mineur bénéficie traditionnellement de règles protectrices et parfois contraignantes destinées à protéger sa personne et son patrimoine. Or, ces dernières se trouvent mises à mal lorsque la qualité d'associé vient se superposer à celle d'incapable. Or il n'est pas rare aujourd'hui qu'un mineur acquière la qualité d'associé, que ce soit lors de la constitution de la société ou en cours de vie sociale. Il peut en effet entrer en société soit par le choix de ses parents, soit en qualité d'héritier d'un associé défunt. En outre, la société, en tant que personne morale sans lien avec les personnes qui la composent, est régie par des règles de fonctionnement qui lui sont propres et qui sont quasiment muettes sur cet associé particulier. II est alors primordial d'apprécier la protection accordée à l'associé mineur dans le cadre particulier des sociétés de famille, c'est-à-dire des sociétés constituées entre membres d'une même famille. Cette protection dépend de la combinaison du droit des mineurs et en particulier des règles de la représentation et du droit des sociétés. Il s'avère que cette combinaison permet parfois aux représentants de l'enfant d'assurer la protection du mineur en exploitant les avantages du droit des sociétés ou en comblant les lacunes. Mais il peut s'avérer que cette combinaison se réalise au détriment des règles de protection et de représentation du mineur. Il est notable que la combinaison des deux corps de règles se réalise différemment selon que la société est constituée dès l'origine autour du mineur ou que la question de l'entrée du mineur se pose après sa constitution. En effet, lorsque la société est conçue autour du mineur, il apparaît que les représentants légaux ont une marge de manoeuvre importante au regard du droit des sociétés : soit qu'il s'agisse de tirer parti des avantages du recours à la forme sociale, soit qu'il s'agisse d'assurer la protection des intérêts du mineur associé que le droit des sociétés ne prend pas en considération sauf exceptionnellement pour lui fermer certaines formes sociales. A l'inverse, lorsque la société subit l'arrivée du mineur, le droit des sociétés manifeste sa supériorité sur le droit de la représentation des mineurs qu'il s'agisse d'organiser les conditions de son acceptation en tant qu'associé ou de lui refuser l'entrée dans la société.C'est ce que la thèse entend démontrer.
Keywords: Famille; Family company; Jeunesse -- Protection, assistance, etc; Mineur; Mineurs (droit); Minor; Protection; Société de famille

Performances des entreprises sénégalaises et réformes dans l'environnement des affaires - Diagne, Idrissa (Université Cheikh Anta Diop, 2022)
L’objectif de ce travail consiste à étudier les réformes et la performance des entreprises sénégalaises. Nous avons à cet effet utilisé l’analyse en composante principale (ACP) suivie d’une classification ascendante hiérarchique (CAH) afin de définir la structure des entreprises sénégalaises et la typologie du tissu des entreprises des pays de référence. Les résultats obtenus nous ont permis de conclure que la taille de l’entreprise est un déterminant de sa position géographique, de son âge et de la participation des capitaux étrangers. Toutefois, aucun lien n’a pu être décelé entre la taille et le régime d’exportation. Ensuite, nous avons pu déterminer que la typologie du tissu des entreprises du Sénégal est loin de refléter celle des pays de référence. De plus, à partir de la méthode de régression linéaire simple (OLS), nous avons relevé que la position géographique, le statut juridique, le transfert de technologie, l’innovation et l’ouverture aux nouveaux marchés, affectent positivement la valeur ajoutée de l’entreprise. En revanche, la taille de l’entreprise, le secteur d’activité, la participation de l’État dans le capital, les garanties sur les prêts influent négativement sur la valeur ajoutée des entreprises. Enfin, à partir de la méthodologie d’analyse comparative, nous avons tiré des leçons sur les meilleures pratiques en termes de réformes. Les résultats suggèrent que l’État du Sénégal devrait davantage s’orienter vers la réduction des coûts afférant à la création d’entreprise, notamment, les frais de notaire, les droits d’enregistrement et la réduction des taxes. L’État devrait également diminuer les coûts de l’énergie, les pertes énergétiques et se réorienter davantage vers le mix-énergétique. En outre, il pourrait améliorer l’accès aux financements à travers le renforcement de l’information sur le crédit, l’acquisition d’actifs et la règle de l’insolvabilité. L’État pourrait par ailleurs renforcer le développement des infrastructures, notamment, aéroportuaire, ferroviaire. D’autre part, la mise en œuvre d’une stratégie nationale de réformes foncières devrait lui permettre de sécuriser le foncier. L’accent devrait être mis ainsi sur l’enseignement professionnel, à l’image du Rwanda et doter le pays d’un système intégré d’informations sur l’emploi. Afin de renforcer la compétitivité des entreprises sénégalaises, l’État gagnerait à renforcer un système national intégré de qualité, et à promouvoir le “label made in Sénégal” à l’image du Rwanda et de l’Éthiopie.
Keywords: Affaires; Entreprise (performance); Entreprise (taille); Secteur manufacturier; Sénégal; Valeur ajoutée

Şirketler hukukunun geleceği üzerine bir inceleme: Şirket yönetiminde yapay zekâ - Bora Çinar, Sevda (Akdeniz Üniversitesi, 2022)
Yapay zekâ teknolojileri, insan unsurunun egemen olduğu pek çok alanı etkisi altına almaya hazırlanmaktadır. Bu alanlar arasında tıp, hukuk, eğitim, mühendislik olduğu gibi ticaret de bulunmaktadır. Yapay zekâ teknolojileri, özellikle şirketler hukukunun geleneksel yapısını kökünden sarsacak yeni bir ticari düzen ve anlayış yaratma yolundadır. Karar alma süreçlerini otomatikleştiren yapay zekâ teknolojilerinin verimliliği ve hızı, şirketlerin bu sistemleri geliştirerek pazarlamalarının yanı sıra bizzat şirket bünyelerine katarak kullanma eğilimi göstermelerine de yol açmaktadır. Bu şekilde kendi kendini besleyen bu döngü, yapay zekâ alanına sermaye yapısı güçlü şirketlerin yönelmesini ve araştırma kapsamının gittikçe genişletilmesini sağlamaktadır. Şirketlerdeki bu yönelim neticesinde, hızla gelişen yapay zekâ teknolojilerinin geleneksel şirket yapılarını etkileyebilme potansiyelinin yükselmesi olgusu, şirketler hukukunun geleceği üzerine bir inceleme yapılması gerekliliğini ortaya çıkarmaktadır. Çalışmamızda şirket yönetiminde yapay zekâ teknolojilerinin kullanımına ve bunun hukuki sonuçlarına odaklanılmakta ve konu dört temel bölüme ayrılarak incelenmektedir. Giriş bölümünde kısaca çalışmanın konusu, önemi, amacı, kapsamı ve sistematiği açıklanmakta, yapay zekâ ve şirket yönetiminin kavramsal çerçevesine yer verilmektedir. Birinci bölümde şirketler hukuku ve yapay zekâ teknolojilerinin etkileşimi incelenmektedir. Bu bölümde yapay zekâ teknolojilerinin ticaret hukuku ve şirketler hukuku ile etkileşimi incelenmekte, dijitalleşmenin şirketler hukukuna etkileri, özellikle şirket yapılarındaki ve menfaat çatışmalarındaki dönüşüm çerçevesinde ele alınmaktadır. İkinci bölümde, şirket yönetiminde yapay zekâ teknolojilerinin kullanılması bir süreç olarak incelenmektedir. Kullanım kararı alınmasından başlamak üzere, şirkete uygun yapay zekâ teknolojilerinin edinimi ve bu teknolojilerinin şirket yönetiminde kullanılma yöntemlerinin araştırıldığı bu bölümde, teknik, hukuki ve ticari başta olmak üzere ilgili beklenti ve belirsizlikler araştırılmaktadır. Üçüncü bölümde şirket yönetiminde yapay zekâ teknolojilerinin kullanılmasının hukuki sonuçları ve hukukun bu dönüşümden nasıl etkileneceği üzerinde durulmaktadır. Son bölümde ise yönetimin geleceği üzerine düşüncelerin yer altığı bir karar ağacı tasarımı içeren interaktif bir bölüme yer verilmektedir. Artificial intelligence technologies are preparing to influence many human-dominated and human-related fields. These fields include medicine, law, education, engineering as well as commerce. Artificial intelligence technologies are on the way to create a new commercial order and understanding that will shake up the traditional structure of corporate law. In particular, the efficiency and speed of artificial intelligence technologies that automate decision-making processes have led companies to tend to use these systems both by developing and marketing them and by incorporating them. In this way, this self-sustaining cycle has led companies with strong capital structures to move towards the field of artificial intelligence, and the scope of research has been gradually expanded. This orientation in companies and the high potential of rapidly developing artificial intelligence technologies to affect traditional company structures have revealed the necessity of conducting an examination on the future of company law. Our study focuses on the use of artificial intelligence technologies in company management and its legal consequences, and the subject is examined under four main sections. In the introduction, the subject, importance, purpose, scope and systematics of the study are briefly explained, and the conceptual framework of artificial intelligence and company management is given. In the first part, the interaction of corporate law and artificial intelligence technologies is examined. In this section, the interaction of artificial intelligence technologies with commercial law and company law is examined, the effects of digitalization on corporate law are discussed, especially within the framework of the transformation in company structures and conflicts of interest. In the second part, the use of artificial intelligence technologies in company management is examined as a process. In this section, where the acquisition of artificial intelligence technologies suitable for the company and the methods of using these technologies in company management are investigated, starting from the decision to use, all technical, legal and commercial expectations and uncertainties are investigated. The third chapter focuses on the legal consequences of the use of artificial intelligence technologies in company management and how the law will be affected by this transformation. In the last part, there is an interactive section that includes a decision tree design with thoughts on the future of management.
Keywords: AI; Anonim şirketler; Artificial Intelligence; Bilgi ve belge yönetimi; Bilgi yönetim sistemi; Bilgi yönetimi; Capital companies; Commercial companies; Financial data management system; Finansal veri yönetim sistemi; Hukuki sorumluluk; Information and records management; Information management; Information management system; Institutional responsibility; Inteligência artificial; Intelligence Artificielle; Joint stock company; Kurumsal sorumluluk; Legal responsibility; Sermaye şirketleri; Ticari şirketler; Yapay zeka

Yönetim kurulu üyelerinin şahsî sorumluluğuna ilişkin davalarda maddî hukukun usûl hukukuyla etkileşimi - Eski̇ocak, Ali (Galatasaray Üniversitesi, 2022)
Les membres du conseil d'administration, qui sont l'organe représentatif et exécutif de la société anonyme, sont investis de pouvoirs et d'attributions étendus à tous les stades de leur activité (Code de Commerce turc art. 365, art. 374). En cas de perte résultant de la violation de ces obligations, il est inévitable que la responsabilité soit mise en avant. Ceci est principalement une conséquence naturelle de la règle générale de "l'équilibre autorité-responsabilité". Dans ce contexte, l'existence et l'effectivité des actions en responsabilité ont un rôle dissuasif pour que les administrateurs ne manquent pas à leurs obligations. D'autre part, en raison du principe de la responsabilité limitée avec les actifs contre les créanciers de la société anonyme (Code de Commerce turc art. 329/1), la protection des actifs est importante pour empêcher les créanciers de subir des pertes. De plus, la question de la responsabilité revêt une importance particulière au regard des principes de gouvernance d'entreprise. Parce que la comptabilité et la responsabilité sont les éléments clés du principe de gouvernance d'entreprise dans les sociétés anonymes qui sont les acteurs les plus importants de la vie économique d'aujourd'hui. Par conséquent, des réglementations détaillées prises en vertu du Code de Commerce turc concernant les obligations et les responsabilités des membres du conseil d'administration; en outre, les dispositions relatives aux poursuites en responsabilité ont été réglementées de manière plus détaillée et systématique et des changements importants ont également été introduits à cet égard. Dans ce cadre, un régime de responsabilité spéciale a été institué pour les administrateurs en dehors des dispositions de responsabilité générale, tandis que les articles 549 à 552 du Code de Commerce turc réglementent la responsabilité spéciale, l'article 553 et les articles suivants du Code de Commerce turc réglementent les dispositions relatives à la responsabilité générale. Ces articles sont relativement larges et complets par rapport à l'ancien code. Diverses études monographiques ont été réalisées en matière de responsabilité juridique des membres du conseil d'administration et ce sujet a été largement examiné dans les travaux sur le droit des sociétés anonymes. Cependant, l'aspect droit matériel de la responsabilité juridique a été principalement examiné dans la doctrine mais les questions liées aux actions en responsabilité et l'aspect procédurale de l'action ont trouvé une place limitée dans la doctrine. Les expressions similaires sont souvent utilisées concernant la nature du droit d'action des actionnaires et créanciers, mais l'aspect procédurale n'est généralement pas examiné avec une explication détaillée, des analyses et une caractérisation. Cependant, cette question est étroitement liée à des questions importantes telles que la relation entre les demandeurs, la litispendance, le jugement définitif, l'exécution du jugement et les caractéristiques des défenses. Dans notre étude, en raison de l'importance des actions en responsabilité et de l'augmentation du nombre des actions en pratique, nous essayons d'expliquer les caractéristiques de l'action en responsabilité (l'aspect procédural) ainsi que l'aspect du droit matériel. Cependant, notre étude n'est pas une thèse de procédure civile, c'est une thèse de droit matériel et il vise à examiner les questions liées au droit procédural en commençant par la nature de la responsabilité, l'engagement de l'action jusqu'à l'exécution du jugement définitif rendu. En conséquence, le sujet de notre étude est de décrire l'aspect de droit substantiel de l'action en responsabilité et d'examiner les domaines où la responsabilité des membres du conseil d'administration intersecter avec le droit procédural. Donc l'objectif de cette étude est l'aspect de droit substantiel de la responsabilité. Les problèmes procéduraux sont examinés dans cette perspective. La responsabilité civile des membres du conseil d'administration a été examiné conformément à l'article 553 et les dispositions suivantes. L'analyse a été faite pour les personnes qui ont le droit d'action avant la déclaration de faillite, mais pas pour les autres qui ont le droit d'action après la déclaration de faillite (administration de la faillite, créanciers). La responsabilité des membres du conseil d'administration et des dirigeants a été prise en considération. Par ailleurs, la responsabilité résultant de la fondation, les cas particuliers de responsabilité régis par l'article 549 et suivants du Code de Commerce turc, la responsabilité de contrôleur qui est régie par l'article 554 du Code de Commerce turc, l'action particulière en responsabilité régie par l'article 193 du Code de Commerce turc, l'action en responsabilité à l'égard d'un groupe de sociétés régi par l'article 202 et les dispositions suivantes du Code de Commerce turc et la révocation des personnes responsables entre elles selon leurs relations internes (action en révocation) sont exclues du champ de cette étude. Notre étude, préparée dans ce contexte, se compose de cinq grandes parties, dans la première partie, les principes de l'aspect droit matériel de l'action en responsabilité ont été examinés. Dans ce cadre, les réglementations légales antérieures et nouvelles en matière de responsabilité, les innovations apportées par la Code de Commerce turc, la base juridique (la source), le but, l'objet, l'intérêt qu'elle protège, ses éléments, sa relation avec divers actions et institutions et ses caractéristiques sont important. La source de responsabilité est basée sur la relation contractuelle entre les membres du conseil d'administration et la société, et les éléments de responsabilité sont l'illégalité, le dommage, le lien de causalité et la faute. La responsabilité des membres du conseil d'administration appartient à l'organe de gestion, est personnelle et fondée sur la faute. Sur cette note, la présomption de responsabilité a été révoquée et le fardeau de la preuve repose sur le demandeur. Alors que le principe de solidarité différenciée a été inclus dans l'article 557 du Code de Commerce turc, il a été mis l'accent sur l'application des dispositions de relation de causalité ainsi que les articles 51-52 du Code des Obligations turc. En ce qui concerne le devoir de diligence, la méthode de référence indirecte au devoir de diligence de l'employé qui était régie par l'article 320 du précédent Code de Commerce a été abandonnée par l'article 369 du Code de Commerce turc, et le devoir de diligence a acquis l'objectivité par l'adoption de « business judgement rule (agir avec diligence, bonne foi et loyauté en decision de gestion)». En outre, dans l'exposé des motifs de l'article, il a été clairement indiqué que le critère de prudence sont pertinents avec la « business judgement rule» Le devoir de diligence est lié à des éléments d'« illégalité » et de « faute ». Par conséquent, cet article signifie l'objectivation de la faute. De ce fait, la frontière entre les éléments d'illégalité et de faute est devenue encore plus incertaine. La délégation de gestion (art.367 du Code de Commerce turc) est une situation qui a un impact sur la responsabilité, avec une délégation valable il y aurait partage responsabilité primaire - responsabilité de surveillance (art. 553/2 du Code de Commerce turc). La nouvelle règle, régie par l'article 557/2 du Code de Commerce turc qui prévoit qu'une action en justice peut être intentée pour l'ensemble du dommage et qu'il peut être demandé au juge de déterminer l'indemnisation de chaque défendeur dans une même action en justice, est importante pour fixer qu'il n'est pas nécessaire que le demandeur tienne compte du principe de solidarité différenciée, et que ce principe est une règle qui ne s'adresse qu'au juge et à la décision qu'il établira. Dans la deuxième partie, les caractéristiques du droit d'intenter une action en responsabilité, les parties de l'action et les modalités d'exercice du droit d'action sont discutées. La caractéristique du droit d'action qui pourrait être exercé par d'autres personnes que la société est importante. Le résultat est étroitement liée aux questions critiques telles que les défenses qui pourraient être invoquées par les défendeurs, et avec quelles défenses pourraient être invoquées contre quel demandeur, la relation entre les demandeurs, la litispendance, le jugement définitif, l'exécution du jugement. Après une évaluation détaillée, notre opinion est que les actionnaires et les créanciers ont chacun individuellement un droit substantiel d'engager une action en responsabilité. En outre, la manière d'exercer le droit de la demande réglementé par la loi est également importante. Étant donné qu'il n'y a pas de disposition ou de déclaration restrictive dans la loi concernant la manière de demande du dommage de l'entreprise, il est également possible d'appliquer tous les recours disponibles en vertu du droit de la procédure civile, de l'exécution et de la faillite. Il est possible de demander des mesures provisoires. Bien qu'il existe une réglementation générale quant aux parties à l'action en responsabilité dans la loi, il est important d'examiner ce sujet. A cet égard, l'action intentée par l'actionnaire avant la faillite n'est soumise à aucune condition. Le montant (ratio) de l'action (la part) n'est pas important. En ce qui concerne le défendeur, les défendeurs sont comptés dans la loi. A ce propos, il est important de déterminer qui entrera dans le champ d'application du concept de « dirigeants», qui est réglementé pour être responsable aux côtés des membres du conseil d'administration. La position des personnes qui ont le droit d'action peut varier selon les avis sur la caractéristique du droit d'action. A notre avis, il n'y a pas d'obstacle légal au dépôt d'actions en responsabilité distinctes par des personnes ayant droit d'action, et cette situation ne constitue pas une litispendance. Dans la troisième partie de notre étude, les instruments de défense relatifs aux actions en responsabilité et à la question de la preuve sont abordés. Les moyens de défense sont importants en ce qui concerne l'instance pendante, la détermination de l'existence des éléments de responsabilité et le calcul du montant de l'indemnité. Parmi les conditions d'action, en tant que moyens de défense en matière de droit procédural, la décision de l'assemblée générale et l'intérêt à agir revêtent une importance particulière. À notre avis la décision de l'assemblée générale devait être recherchée comme condition d'action. En outre, bien que l'intérêt à agir soit une condition générale d'action, il prend plus d'importance pour le cette étude, car dans les actions en responsabilité l'événement qui constitue une violation de l'interdiction de l'abus de droit (art. 2 Code Civil turc). En outre, l'adoption du principe de solidarité différenciée a accru l'importance des motifs de défense individuels. Les motifs matériels de la défense peuvent être très divers, tels que le fait de ne pas être investi d'un organe de gestion, la libération, la prescription, la forclusion, l'exécution du devoir de diligence et la délégation de pouvoir. De plus, comme dans tous les procès, la question de la preuve est également très importante dans les actions en responsabilité. Cependant, un système de preuve spécial et une méthode de preuve n'ont pas été prévus en termes des actions en responsabilité. Par conséquent, des questions telles que la charge de la preuve, l'objet de la preuve, l'échelle de la preuve et les preuves propres doivent être déterminées en tenant compte des caractéristiques spécifiques de l'action en responsabilité, et cela a été examiné dans ce cadre dans notre étude. Dans le quatrième chapitre, le déroulement du procès, le jugement et l'exécution du jugement sont expliqués. En particulier, l'accent mis sur le lien de causalité et l'acceptation du principe de solidarité différenciée avec de nouvelles dispositions obligent le juge à procéder à un examen précis. Dans ce contexte, des questions telles que l'impossibilité du contrôle d'opportunité, la mise en œuvre du principe de solidarité différenciée et la prise en compte de la situation des responsables, qui ne sont pas parties au procès, sont les aspects originaux de la procédure. L'effet du jugement à la fin de l'action est également un sujet discuté dans la doctrine. À notre avis, le jugement ne constituera pas res iudicata (l'autorité de la chose jugée) pour les autres actions en responsabilité et les actions en révocation. Cependant, il convient de noter que l'effet de l'intervention en cas de dénonciation d'instance et d'intervention accessoire, pourrait être important en termes d'action en révocation, et de fait, il peut avoir un effet plus important que res iudicata. Une autre question importante est celle de savoir qui a le pouvoir d'exécuter le jugement et les possibilités dans cette question. Le point le plus prénant ici est que le droit de réclamation de l'actionnaire (le demandeur) comprend le pouvoir d'exécuter le jugement, mais le paiement perçu au stade de l'exécution doit être versée à la société. Dans le cinquième chapitre, quelques situations particulières liées aux actions en responsabilité sont examinées. Dans ce contexte, il a été analysé que l'effet du recouvrement partiel ou total du dommage sur les autres parties responsables dans le cadre de diverses possibilités, la transaction et le désistement d'action (la validité et caractère obligatoire), l'examen de la libération d'une ou plusieurs des personnes responsables au sens de l'article 166/3 du Code des obligations turc, la pertinence de la révocation dans le cadre de l'action en responsabilité et les opérations collusoires de l'entreprise dans le cadre de l'action en responsabilité. Notre avis a été indiqué en conjonction avec l'analyse des arguments de la doctrine et de la pratique sur ces questions.
Keywords: Borçlar hukuku; Cases; Davalar; Faulty liability; Hukuki sorumluluk; Kusurlu sorumluluk; Law of obligations; Legal responsibility; Maddi hukuk; Members of the board directors; Procedural law; Responsibility; Sorumluluk; Substantive law; Turkish Commercial Code; Türk Ticaret Kanunu; Usul hukuku; Yönetim kurulu üyeleri

Anonim ortaklıkta yönetim kurulu üyesinin rekabet yasağı - Günaydin Gülteki̇n, Burcu (Galatasaray Üniversitesi, 2022)
This subject matter of this work is the prohibition of competition with the company of members of board of directors in joint stock companies under art. 396 of the Turkish Commercial Code. The prohibition of competition is a limitation on the commercial activities and the freedom of competition of a restricted party who has access to information, means or resources due to the legal relationship between parties which grant the restricted party a leverage in competition with the other. The core idea underlying the prohibition of competition is the necessity to protect the party benefiting from this prohibition against competitive activities of the restricted party. The prohibition of competition bans the restricted party from establishing competition with the party benefiting from the prohibition through competitive actions, ultimately from becoming the competitor of the beneficiary. The said competition relationship will occur in the event the services or products serving the same or similar needs are provided to the entirety or part of the same customers or customer group. Board members in joint stock company, having the prevailing right of access to all information and resources of the company leads to the risk that it may use this power for its own or other parties' benefit instead of that of the company. Hence, the prohibition of competition on board members regulated under article 396 of the Turkish Commercial Code is one of the concrete examples of the duty of loyalty of a board member towards the company aiming to prevent such usages prioritizing the benefit of the member or of a third person over that of the company. The focal point of this work is the determination of the scope of application and conditions of this prohibition as a whole. The first chapter of this thesis aims to convey the conceptual basis of the prohibition of competition. In this scope, we first assessed the economic and legal basis of competition. Economic competition is the race/competition of two or more market actors in a specific market in order to engage in a transaction with its counterparty in the market through offering better prices, conditions, goods or services in order to be superior from its competitors. However, the intention to supersede its competitors and the efforts for this purpose may result in the misuse of the right to compete or in an act limiting or eliminating the competitive environment. The Republic of Turkey provides for a constitutional protection over a person's right to engage in commercial activities and, although not expressly regulated, right to compete. However, as is the case for all rights and liberties, the right and liberty to compete cannot be exercised without any limitation. Second, the scope of the prohibition of competition is assessed. In this regard, we tried to determine the elements of the prohibition of competition, its definition, and its legal categorization. Moreover, a comparison of the prohibition of competition with the provisions governing unjust competition aiming to establish honest and undisrupted competition as well as with the rules of Competition Law aiming to prevent disruption of competition through restrictive actions is provided in order to specify the prominent characteristics of the prohibition of competition. Third, the attributes of the provisions governing the prohibition of competition are assessed. Provisions governing prohibition of competition which do not relate to the public order but to the internal relations of parties, and which serve the personal benefit of the beneficiary, are not of a peremptory nature. The prohibition of competition, which materially limits the liberty of engaging in commercial activities protected under the constitutional law, is of an exceptional nature and hence the provisions governing the prohibition of competition need to be construed in a limited manner. Fourth, the prohibition of competition can be regulated in the letter of a contract through mutual agreement thereon by its parties, or the legislator occasionally provides for a legal provision governing the prohibition of competition by attributing a special importance to this prohibition with respect to a specific relationship between the parties. Last, in this first chapter, we identify the reflections of this prohibition of competition within the scope of the Law of Obligations, and the Law of Corporations. The second chapter of this work takes into consideration the reasons of regulating a prohibition of competition on board members, and its scope of application regarding the persons concerned. In this context we first broadly assessed the position of the board of directors, board members and affiliated commercial auxiliaries in a company. Then, the legislative provisions respectively of German Law, Swiss Law and Turkish Law governing the board members' prohibition of competition are specified. While in German Law, just as is the case in Turkish law, the prohibition of competition of board members is stipulated in § 88 of the German Stock Corporation Act, the Swiss Law does not regulate this prohibition of competition of board members with a statutory provision, nonetheless, this prohibition is accepted by the scholars. Thereafter, the reason for regulating the prohibition of competition of board members is assessed. In this scope, the duty of loyalty of a board member arises from the legal relationship between the member and the corporation being based on the principle of trust. The member must refrain from conflicting its interests with the interests of the corporation, in other words, from conflict of interests, due to its duty of loyalty. When the member engages in competition with the company, the interests of the company and the board member conflict with each other. The member is in a considerably advantageous position in this conflict compared to the company, due to the information and resources to which it has access thanks to its position within the company. For this reason, the duty of loyalty aiming to prevent the conflict of interest between the company and the member lies at the basis of the board member's prohibition of competition. Lastly, in this chapter, the persons subject to the prohibition of competition pursuant to article 396 of the Turkish Commercial Code are identified. In this respect, the members of the board of directors as well as persons to whom management authorities are delegated fall within the scope of the ratione personae of article 396 of the Turkish Commercial Code. The commercial representatives and commercial proxies of a company are prohibited from competition pursuant to the prohibition of competition regarding commercial auxiliaries pursuant to article 553 of the Turkish Code of Obligations. Whereas a shareholder is not subject to the prohibition of competition with the company; this prohibition may only be regulated by a contract subject to the Law of Obligations. Furthermore, when evaluating the prohibition of competition of shareholders, whether the shareholder has a duty of loyalty to the company has been assessed under German Law, Swiss Law and Turkish Law. The third chapter of this work sets forth the scope of application of the prohibition of competition of board members with respect to its subject matter, place, and time. In order for a board member to violate the prohibition of competition with the company, the member must engage in an activity competing with the company. Pursuant to the first paragraph of article 396 of the Turkish Commercial Code, two types of competitive actions of board members are banned. The first type is the member engaging in an action which is a commercial transaction that falls within the scope of the field of activity of the company, on behalf of itself or a third party. Accordingly, all kinds of acts and actions of the member realized on behalf of itself or third parties which fall within the scope of activity of the corporation would constitute the breach of the prohibition. The scope of this prohibition also encompasses joining the managing body of another corporation. Furthermore, depending on the specifics of a concrete case, the same member being an employee of a competitor corporation under a service contract, or providing consultancy services or extending facilities to a competitor, or benefiting from a job opportunity which belonged to the company may also be construed to be within the scope of the prohibition of competition. The second type is the member being engaged as a partner with unlimited liability in a corporation engaging in the same types of commercial activities. In this regard, if a member becomes a partner of an ordinary partnership or a collective corporation, or a partner with unlimited liability of a commandite corporation, which engages in activities that fall within the scope of activities of the joint stock company, the prohibition will be breached. The prohibition of competition of the board member with the company may be lifted by an authorization granted by the general assembly pursuant to article 396 of the Turkish Commercial Code. This permission to compete to be granted to a board member may be in the form of a prior approval or a later acknowledgement (ratification), in an expressed or implied manner. As a result of the member being permitted to compete, article 396 of the Turkish Commercial Code will no longer apply even if the member engages in activities in competition with the company. The prohibition to compete of the board member lasts for the duration of the board membership. Once the membership ends, the parties must conclude an agreement in order to continue the prohibition of competition. The said agreement regarding the prohibition of competition will be subject to form requirements to be valid. Pursuant to the liberty of contract inherent in the Law of Obligations, the parties may freely execute an agreement regarding the prohibition of competition, provided they comply with the provisions in paragraph 2 of article 23 of the Civil Code or article 26 and first paragraph of article 27 of the Turkish Commercial Code. The prohibition to compete of board members is valid as long as they execute the activities of the company, and within the geography where the clientele of the corporation is located. The fourth and last chapter of this work is devoted to the consequences of breach of the prohibition to compete by a board member. If a member of the board of directors violates this prohibition, the consequence of this breach is regulated in the first paragraph of art. 396 of the Turkish Commercial Code. Accordingly, the joint stock company is granted with certain elective rights. Such that, primarily the company may request compensation from the member in breach of the prohibition of competition. Second, it may be requested that the transaction is deemed concluded on behalf of the joint stock company, third, that the benefits arising from the agreement the member concludes on behalf of third parties belong to the joint stock company. In its request for compensation, the joint stock company must prove the action of the board member violating the prohibition of competition, that the corporation suffered losses from this activity, and the causal link between this activity and the loss of the company. In its request for the transaction to be deemed concluded on its behalf, the company requests for the economic consequences of the transactions the member concluded in violation of the prohibition of competition on its behalf. In its request for the benefits arising from the agreement, the company requests that benefits arising from the agreement the member concluded on behalf of third parties are left to itself. At this point, we materially benefited from the German doctrine and jurisprudence in explaining the claims requesting that a transaction is deemed concluded on behalf of the company and that the benefits from the transactions are left to the company. These rights granted in the first paragraph of article 396 of the Turkish Commercial Code are not cumulative but elective. Pursuant to the second paragraph of article 396 of the Turkish Commercial Code, the authority to chose one of the elective rights granted to the company belongs to the members of the board of directors, excluding the member having violated the prohibition of competition. The third paragraph of article 396 of the Turkish Commercial Code regulates a dual prescription period of three months and one year. These periods are with respect to the exercise by the company of its elective right to make a claim. The first is the period of three months whose commencement will be determined based on the knowledge by other members that an action subject to the prohibition of competition is realized or that a board member joined another corporation. The second period is the period of one year commencing from the realization of the action violating the prohibition to compete. This one-year period is independent from other members' knowledge that the prohibition to compete has been breached. The corporation may raise other claims against the member violating the prohibition of competition which are not stipulated under article 396 of the Turkish Commercial Code. Accordingly, the corporation may request that the member violating the prohibition of competition through joining a competing corporation as a partner with unlimited liability or joining the managing body of a competitive corporation resigns from this corporation or managing body. Further, the company may dismiss the member violating the prohibition of competition from board membership. Again, the company may initiate a lawsuit to cease the ongoing violation of the prohibition of competition by a board member, or a lawsuit of preclusion prior to probable breaches which have not yet occurred. In this chapter, lastly, the fourth paragraph of article 396 of the Turkish Commercial Code is assessed. This paragraph regulates that provisions governing liability of the members of the board of directors are reserved. This is a new provision which was not present in the abrogated Turkish Commercial Code no. 6762, newly introduced under the Turkish Commercial Code. In this context, we tried to determine the purpose and characteristics of this provision and concluded this work.
Keywords: Administrateurs; Anonim şirketler; Board of directors; Competition prohibition; Concurrence (interdiction); Joint stock company; Members of the board directors; Rekabet yasağı; Société par actions; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yönetim kurulu; Yönetim kurulu üyeleri

Hâkim pay sahibinin azınlığı şirketten çıkarma hakkı (Squeeze-out) - Keski̇n, Harun (Ankara Üniversitesi, 2022)
Klasik anlamdaki şirketten çıkarma düzenlemeleri, "haklı sebep" temeline dayanmaktadır. Bu düzenlemelerin en tipik özelliği, düzenlemiş oldukları çıkarma hakkı ile şirketin feshi kurumu arasında bir bağlantıya yer vermiş olmalarıdır. Bu bağlantı, haklı sebebe dayalı çıkarma düzenlemelerinin hizmet ettiği birincil amacı da ortaya koymaktadır: Şirketin devamlılığını sağlamak suretiyle ortaklar arasındaki menfaatler dengesi korumak. Türk hukukuna 6102 sayılı Türk Ticaret Kanunu ve 6362 sayılı Sermaye Piyasası Kanunu ile kazandırılan "squeeze-out" müessesesi ise daha farklı bir kuramsal temele dayanmaktadır. Bu müessese ile, şirkette genellikle %90-95 arasında nitelikli bir pay ve/veya oy oranına ulaşmış olan hâkim pay sahibine, azınlığın paylarını herhangi bir sebep göstermeden iktisap edip, onu şirketten çıkarma hakkı tanınmıştır. Böylece çıkarmanın ekseni, "haklı sebep" olgusundan "hâkimiyet" olgusuna kaymıştır. Kanun koyucuların bu şekilde bir çıkarma hakkını öngörmelerindeki temel sebep ise kurumsal nitelikte bazı amaçları gerçekleştirmek isteyen hâkim konumdaki pay sahiplerine bir imkân sunmaktır. Tezimizde, klasik anlamdaki çıkarma müesseselerinin dayanmış olduğu kuramsal temelden ayrılan "squeeze-out" kurumunun kuramsal temeli, düzenlemenin hangi amaçlarla öngörüldüğü meseleleri ele alınmakta; bu bağlamda, kurumun karşılaştırmalı hukuktaki ne şekilde düzenlendiği, kurumun ortaya çıkardığı sorunlar ve bu sorunların çözümüne yönelik önerilere yer verilmektedir. The classic rules designed for exclusion of a partner has a simple theoretical basis: A/an justified/objective reason (or in other words "good cause"). The most typical feature of these rules is they build a bridge between the exclusion right and the dissolution of the company. This bridge also shows the the primary purpose served by these rules which is to maintain the balance of interests among the partners by ensuring the continuity of the company. In comparison with the classical rules, the "squeeze-out" rules which have been introduced into Turkish law with the Turkish Commercial Code No. 6102 and the Capital Markets Law No. 6362, have a different theoretical basis. The controlling shareholder who has reached a qualified percentage of capital and/or voting rights (usually %90-95), has been granted the right to acquire the minority's shares without asserting any justified reason and exclude him from the company. Thus the idea behind the exclusion has been changed from "good cause" to the "dominance/control". The main reason for designing such an exclusion right is to provide an opportunity to the controlling shareholders trying to achieve institutional objectives in the company. In our thesis, the theoretical basis of the "squeeze-out" rules and the reasons for designing such a new exclusion right will be examined within the framework of other squeeze-out rules in comparative law. Within this context, the most common problems in squeeze-outs and suggestions for solving these problems are analyzed.
Keywords: Actionnaire majoritaire; Actionnaire minoritaire; Anonim şirketler; Azınlık hakları; Capital companies; Dismissal from the partnership; Dominant position; Exclusion; Hakim durum; Joint stock company; Kanunlar 6362 sayılı; Laws 6362 numbered; Limited company; Limited şirketler; Minority rights; Ortaklıktan çıkarılma; Satın alma hakkı; Sermaye şirketleri; Société commerciale; Squeeze-out right; Turkish commercial law; Türk ticaret hukuku

Anonim şirketlerde ilişkili taraf işlemleri - Şi̇mşek, Bahar (İstanbul Üniversitesi, 2022)
İlişkili taraf işlemlerine ilişkin özel düzenlemelerle şirketin varlıklarının ilişkili taraflara aktarılması ve şirketin ve şirketin bütün menfaat sahiplerinin hâkim pay sahipleri ve yöneticiler tarafından sömürülmesinin engellenmesi amaçlanır. Bu amaçla ilişkili taraf işlemleriyle ilgili Sermaye Piyasası Kanunu'nda etraflıca bir düzenleme getirilmiş ve önemli bazı işlemler için prosedür öngörülmüştür. Çalışmamız, esaslı düzenleme Sermaye Piyasası Kanunu'nda yer aldığı için bu düzenleme temel alınarak şekillendirilmiştir. Ancak sadece halka açık şirket değil; halka kapalı şirketler yönünden de konu incelenmiş, ilişkili taraf işlemi sayılabilecek Türk Ticaret Kanunu'nda ve diğer kanunlarda yer alan diğer düzenlemelere de yer verilmiştir. Tez dört bölümden oluşmaktadır. İlk bölümde ilişkili taraf işlemi kavramı genel olarak açıklanmış, ilişkili taraf işlemleriyle ilgili düzenlemelere neden ihtiyaç olduğu hususu ortaya koyulmaya çalışılmıştır. Bu kapsamda benzer kavramlarla karşılaştırılmış ve Avrupa Birliği ve çeşitli ülkelerde düzenlemeler incelenmiştir. Nihai olarak Türk hukukunda ilişkili taraf işlemlerinin tarihsel sürecine yer verilmiştir. İkinci bölümde yasal düzenlemelerdeki ilişkili taraf ve ilişkili taraf işlemi kavramı ele alınmıştır. Üçüncü bölümde ise ilişkili taraf işlemleriyle ilgili Sermaye Piyasası Kanunu, Türk Ticaret Kanunu ve bazı özel kanunlarda yer alan düzenlemeler incelenmiş, ilişkili taraf işlemleri için öngörülen prosedürel korumalar açıklanmıştır. Dördüncü bölümde ise hukuka aykırı ilişkili taraf işlemlerinin sonuçları incelenmiş ve ilgililerin sorumluluğuna yer verilmeye çalışılmıştır. Special regulations regarding related party transactions aim to prevent the transfer of the assets of the joint stock company to the related parties and thus prevent the exploitation of all the stakeholders of the company by the controlling shareholders and managers. For this purpose, a comprehensive regulation has been introduced in the Capital Markets Law regarding related party transactions and a procedure has been envisaged for some significant transactions. Since the main regulation is contained in the Capital Markets Law, our thesis has been shaped based on this regulation. However, this thesis has not examined the subject only for public companies; it has also examined it in terms of non-public companies, and other regulations in the Turkish Commercial Code and other laws, which can be considered as related party transactions. The thesis consists of four parts. In the first part, the concept of related party transactions is explained in general and the reason for the need for regulations regarding related party transactions is tried to be revealed. In this context, related party transactions have been compared with similar concepts and the regulations in the European Union and various countries have been examined. Finally, the historical process of related party transactions in Turkish law is examined. In the second chapter, the concept of related party and related party transactions as defined in legal regulations is discussed. In the third section, the regulations contained in the Capital Markets Law, the Turkish Commercial Code and some special laws related to related party transactions are examined and the procedural protections provided for related party transactions are explained. In the fourth chapter, the results of unlawful related party transactions are examined and the liability of the related parties is tried to be included.
Keywords: Anonim şirketler; Camouflage of earning distribution; Joint stock company; Société par actions; Turkish capital market; Turkish commercial law; Türk sermaye piyasası; Türk ticaret hukuku; Örtülü kazanç dağıtımı

Anonim ortaklıkta pay sahibinin bilgi alma ve inceleme hakkı - Sümer, Burak (Hacettepe Üniversitesi, 2022)
Anonim ortaklıkta her pay sahibi genel kurulda, yönetim kurulundan şirketin işleri; denetçilerden ise denetimin yapılma şekli ve sonuçları hakkında bilgi alma talebinde bulunma hakkına sahiptir. Ayrıca her pay sahibinin şirketin ticari defterlerini ve yazışmalarını, sorusunu ilgilendiren kısımları ile sınırlı olarak inceleyebilme hakkı bulunmakla birlikte, bunun için genel kurulun açık izni veya yönetim kurulunun bu hususta kararı gereklidir. Pay sahibinin bilgi alma ve inceleme hakkının reddi, talep edilen bilginin şirket sırlarının açıklanmasına veya korunması gereken diğer şirket menfaatlerinin tehlikeye girmesine neden olabilecek ise söz konusu olabilir. Bilgi alma ve inceleme talebinin cevapsız bırakılması, haksız olarak reddedilmesi, ertelenmesi veya pay sahibinin kanunda düzenlendiği şekilde bilgi alamaması halinde, hakkın açılacak bir dava ile mahkeme aracılığıyla kullanılması da mümkündür. Çalışmamız dört bölümden oluşmaktadır. İlk bölümde bilgi alma ve inceleme hakkının genel nitelikleri ile karşılaştırmalı hukuktaki düzenlenme şekli; ikinci bölümde hakkı etkileyen ilkeler ve hakkın düzenlenme amacı; üçüncü bölümde bilgi alma ve inceleme hakkının kullanılması ve hakkın sınırları; dördüncü ve son bölümde ise hakkın ihlalinin hukuki sonuçları ele alınmıştır. At the general meeting, any shareholder of a joint stock company is entitled to information from the board of directors on the affairs of the company and from the external auditors on the methods and results of their audit. Also the company ledgers and business correspondence, limited to the parts about the question may be inspected only with the express authorisation of the general meeting or by resolution of the board of directors. It may be refused where providing it would jeopardise the company's trade secrets or other interests warranting protection. If the request for information and examination is left unanswered, unfairly rejected, postponed or if the shareholder is unable to obtain information as regulated in the law, it is also possible to exercise the right through a lawsuit to be filed. Our study consists of four parts. In the first part, the general characteristics of the right to information and examination and the way it is regulated in comparative law; in the second part, the principles affecting the right and the purpose of regulation of the right; the exercise of the right to receive and review information and the limits of the right in the third part; In the fourth and last chapter, the legal consequences of the violation of the right are discussed.
Keywords: Anonim ortaklıklar; Bilgi alma ve inceleme hakkı; Company law; Incorporated companies; Pay sahipleri; Right to information and examination; Shareholders; Turkish commercial law; Türk ticaret hukuku; Şirketler hukuku

Halka açık anonim şirketler bakımından şirketler topluluğunda ortak nakit ve hizmet kullanımının hukuki sonuçları - Üzeler Demi̇rağ, Rabia Sanem (İhsan Doğramacı Bilkent Üniversitesi, 2022)
Bu çalışmanın temel amacı şirketler topluluğunda yer alan halka açık şirketlerin topluluk şirketleri ile ortak nakit ve hizmet kullanımına yönelik işlemlerinin sermaye piyasası mevzuatı açısından sınırlarının ve hukuki sonuçlarının tespit edilmesidir. Bu doğrultuda sermayenin oluşturulması ve malvarlığının korunması kuralları kapsamında ortak nakit kullanımı uygulamalarının sınırları, ilişkili taraf işlemlerine ilişkin düzenlemeler ve örtülü kazanç aktarımı yasağı çerçevesinde değerlendirilmiştir. İlaveten, şirketler topluluğunda maliyet tasarrufu sağlayan ve topluluğun ortak stratejiler çerçevesinde yönetilmesi bakımından gerekli olan ortak hizmetler nedeniyle yapılan ödemelerin tutarlarının belirlenmesine ilişkin esaslar örtülü kazanç aktarımı yasağı bağlamında ele alınmıştır. Son olarak, hukuka aykırılığa yol açan ortak nakit ve hizmet kullanımı uygulamalarına yönelik Sermaye Piyasası Kurulu'nun müdahale yetkileri ve şirketler topluluğunda hâkim şirketin bağlı şirketin kaybını denkleştirebilmesi olanağının halka açık şirketlerde uygulama alanı bulmasının hukuken hangi hâllerde gündeme gelebileceği irdelenmiş ve halka açık şirketlerin dâhil oldukları şirketler topluluklarında ortaya çıkan menfaat çatışmalarının dengelenmesine yönelik değerlendirme ve düzenleme önerilerinde bulunulmuştur. The main purpose of this study is to determine the legal limits and consequences of the shared use of cash and services within corporate groups for publicly held companies' in relation to capital markets legislation. In this respect, the legal limits of transactions which enables sharing cash among group companies with respect to rules on formation and protection of capital of publicly held companies is reviewed within the context of related party transactions and cases which may result in disguised profit distribution is evaluated. Additionally, the use of shared services in corporate groups which provides significant savings and is necessary for developing common strategies is examined in order to determine which principles must be adhered to while charging for these services with regard to the ban on disguised profit distribution. Furthermore, Capital Markets Boards' intervention powers regarding the shared use of cash and services which results in violation of the law is evaluated and the parent company's opportunity of balancing the disadvantages of the subsidiary is assessed for publicly held companies. Finally, legislative amendments have been proposed in order to balance the conflicts of interest which arises where a publicly held company is part of a corporate group.
Keywords: Anonim şirketler; Capital Market Board; Capital Market Law; Cash flow; Cash management; Cosourcing; Halka açık ortaklıklar; Joint stock company; Nakit akışı; Nakit yönetimi; Ortak kaynak kullanımı; Public held companies; Sermaye Piyasası Kanunu; Sermaye Piyasası Kurulu; Turkish commercial law; Türk ticaret hukuku

Analyse critique des sources et notions du droit musulman et de leur compatibilité avec le droit français : exemples tirés du droit des sociétés - Bouaïcha, Yassine (Université de Rennes 1, 2021)
Les entrepreneurs et chefs d’entreprise musulmans sont voués à évoluer dans leur vie entrepreneuriale : création ou développement de leur activité. Mais afin de démarrer ou de s’agrandir, le chef d’entreprise a souvent besoin d’un prêt afin d’investir dans des outils et produits dans le but de « passer à la vitesse supérieure ». Mais du fait qu’il n’existe toujours pas de prêt halal pour ces personnes, celles-ci sont vouées à rester dans le domaine des TPE et de l’artisanat. Le stade supérieur, bien que le marché leur soit visible et atteignable, leur paraît comme un plafond de verre impossible à briser sans prêt qui convienne à leur éthique. Il convient ainsi d’étudier les instruments juridiques en droit musulman afin d’en déduire la latitude octroyée aux musulmans d’Occident pour cette situation. Cela permettra de confronter ces avis à la législation en vigueur en droit des sociétés, s’agissant entre autres de la constitution de l’apport afin de créer une société.
Keywords: Corporate law; Droit des sociétés; Droit islamique; Droit musulman; Entrepreneuriat; Entrepreneuriat musulman; Finance islamique, Fiqh; Finances -- Pays arabes; Fiqh; Islam -- Aspect économique; Islamic finance; Muslim law; Muslin entrepreneurship; Pays arabes; Usul al fiqh

Execução diferida do contrato em operações de fusões e aquisições (F&A) de sociedades anônimas: análise de aspectos contratuais e societários - Costa, Fernanda Mynarski Martins (Universidade de São Paulo, 2021)
Os contratos de fusões e aquisições no direito brasileiro têm apresentado como técnica de diferimento temporal entre a celebração do acordo global (assinatura, signing) e o adimplemento da obrigação típica (fechamento, closing), uma estrutura contratual originária do common law, resultante de interações entre as seções de cláusulas de condições precedentes (conditions precedents), obrigações de fazer e não-fazer antecedentes ao fechamento (covenants prior to closing) e declarações e garantias ( representations e warranties). A presente tese busca analisar as peculiaridades do transplante dessa técnica ao sistema jurídico brasileiro, a fim de qualificar juridicamente as cláusulas transplantadas bem como identificar os efeitos jurídicos de fase existente entre a assinatura e o fechamento, chamada de período interino (interim period). A primeira parte do trabalho dedica-se a uma análise abrangente da referida técnica. No primeiro capítulo é abordada a contextualização da prática em seu habitat original, a saber: os contratos de aquisição de participação acionária no direito estadunidense. No segundo capítulo, é realizada a qualificação jurídica das cláusulas transplantadas ao direito brasileiro, mediante uma análise funcional e estrutural. A segunda parte do trabalho examina os efeitos das estruturas que compõem o fechamento diferido mediante duas perspectivas. A primeira, objeto do capítulo terceiro, é a contratual. A segunda é a societária, objeto do quarto capítulo.
Keywords: Acquisition; Brasil; Cláusula contratual; Common law; Condition precedent; Contrato comercial; Covenant prior to closing; Deferred closing; Deferred performance contract; Direito comparado; Direito das Obrigações; Estados Unidos; Fusão e aquisição de empresas; Interim period; Mergers & acquisitions; Representations & warranties; Signing and closing; Sociedade anônima

El balance de fusión en las sociedades de capital - Melchor Giménez, Enrique (Universidad de Sevilla, 2021)
La exigencia de un balance para la realización de la fusión ha sido una constante en la regulación de esta operación societaria en el ordenamiento español, desde el RRM de 1919, pasando por las posteriores LSA de 1951 y LSA de 1989, hasta la vigente LME. Pese a tratarse de una institución jurídica de amplio recorrido histórico en la legislación española, aspectos trascendentales como su naturaleza y finalidad han sido objeto de una gran controversia y se han planteado una serie de interrogantes en relación con estos que todavía no pueden ser considerados plenamente resueltos. El régimen vigente, por un lado, mantiene previsiones normativas establecidas originalmente conforme a una concepción de la finalidad del balance de fusión ya superada, que deben ser reinterpretadas a la luz de su significación actual en el proceso de fusión. Por otro lado, se han incorporado a la regulación de la fusión preceptos derivados de las Directivas europeas que responden a planteamientos ajenos a la tradición jurídica española y requieren una interpretación cohesionadora. En la presente investigación se aborda el estudio de la regulación del balance de fusión en las sociedades de capital, dividiendo el trabajo en las siguientes tres partes: La primera parte del trabajo está centrada en el estudio de la evolución jurídica de la regulación española del balance de fusión en las sociedades de capital. Dicho análisis ha sido estructurado en función del desarrollo de la legislación societaria, pese a que otras esferas del derecho, como la legislación fiscal, o el propio desarrollo de la normativa societaria en el ámbito contable, hayan podido tener una marcada incidencia en su evolución. En la segunda parte, se analizan los aspectos sustantivos de la regulación vigente del balance de fusión. El propósito perseguido en esta es dar respuesta a las cuestiones que se plantean en torno a la naturaleza y función del balance en el seno del proceso de fusión. Tales cuestiones, en sí mismas, constituyen los principales problemas interpretativos que suscita la actual regulación. Pero, además, las conclusiones que se alcancen servirán de base para el posterior análisis del conjunto de requisitos formales del balance que deben seguirse para la aprobación y ejecución de la fusión. En la tercera parte, se examinan pormenorizadamente los aspectos formales de la regulación del balance de fusión en la LME. Los capítulos que la componen se establecen atendiendo a las distintas fases del proceso por las que debe transcurrir la modificación estructural. De modo que se marca un recorrido que comienza con la formulación del balance de fusión, en la fase preparatoria, y concluye con la formalización e inscripción de la operación y la posibilidad de impugnar el balance.
Keywords: Derecho mercantil; Fusión de empresas

El derecho de separación del socio por falta de reparto de dividendos en las sociedades de capital cerradas - Pérez Carbó, Pedro Pablo (Universitat de Barcelona, 2021)
El derecho de separación constituye uno de los mecanismos legales alternativos y efectivos para proteger al socio minoritario disconforme con el acuerdo de reparto de dividendos en las sociedades de capital cerradas en España. La mayoría distribuye dividendos encubiertos desleales, destina los beneficios sociales a reservas o consigna a dividendos una cantidad inferior al mínimo legal. Sin embargo, la acción de impugnación de estos acuerdos es insuficiente para tutelar al socio minoritario e impedir la reiteración de estas conductas. En el año 2011 la Ley de Sociedades de Capital incorporó el derecho de separación del socio minoritario con causa en la limitación de su derecho al dividendo. En diciembre del año 2018, la modificación de este precepto equilibró los intereses entre la mayoría y la minoría con prevalencia del interés social para proteger el tejido empresarial en tiempos difíciles. Por eso, esta tesis doctoral analiza los problemas interpretativos funcionales y sistemáticos de este particular derecho de separación y obtiene tres descubrimientos esenciales. En primer lugar, el derecho al dividendo es un derecho concreto de crédito del socio frente a la sociedad basado en el ánimo lucrativo del contrato social. En segundo lugar, la naturaleza jurídica del derecho de separación se fundamenta en el incumplimiento del contrato social y la protección de la sociedad y del socio minoritario. En tercer lugar, este es un derecho disponible configurable estatutariamente, derogable por la mayoría y renunciable por el socio. Las conclusiones de este estudio destacan tres cuestiones principales. Por un lado, la opresión al socio minoritario resulta de la vigencia del principio de la mayoría, las restricciones a la transmisibilidad de las acciones y participaciones sociales y la inexistencia de un mercado para su transmisión onerosa. Por el otro, los presupuestos subjetivos de este derecho se circunscriben a las sociedades de capital cerradas anónimas y de responsabilidad limitada por tiempo indefinido. En especial, excluyendo a las sociedades cotizadas, con acciones admitidas a negociación en un sistema multilateral, en concurso, con acuerdos de refinanciación y a las anónimas deportivas. Finalmente, los presupuestos objetivos estriban en la existencia de cinco ejercicios desde la inscripción de la sociedad, beneficios distribuibles y beneficios en los tres ejercicios anteriores. Además, la falta de reparto del dividendo mínimo del veinticinco por ciento de los beneficios sociales legalmente distribuibles. También, incluyen a los grupos de sociedades cuando la sociedad matriz está obligada a formular cuentas consolidadas.
Keywords: Civil law; Ciències Jurídiques; Commercial law; Corporate governance; Derecho civil; Derecho mercantil; Dret mercantil; Dret privat; Econòmiques i Socials; Gobierno de la empresa; Govern corporatiu

The influence of capital structure and profitability on the solvency of nascent SMEs - Amoa-Gyarteng, Karikari (University of Johannesburg, 2021)
Even though small and medium enterprises contribute significantly to the growth of national economies, they are vulnerable in their early stages and may fail. Hence younger businesses are more likely to fail than more established ones because they face complex challenges that may limit their viability. This is a notion established in the liability of newness framework. According to the liability of newness concept, the precarious existence of emerging organisations is due to difficulties in managing relationships among strangers, not quickly assembling resources, and not coping with difficult environments, among other issues. All these elements notwithstanding, previous literature suggests that small businesses can, and sometimes do engage in techniques or approaches to help reduce the liability of newness, such as raising adequate capital. This study suggests that not only is adequate capital important but that the right mix of capital also results in higher solvency, thereby mitigating the liability of newness. Because the various funding forms have distinct advantages and disadvantages, an appropriate capital structure reduces the cost of financing while increasing the value of the firm. This study also advances the idea that profitable businesses are productive and financially strong, and thus nascent enterprises with high profitability can minimise the liability of newness. As a result, the study sought to examine the influence of capital structure and profitability on the solvency of nascent small and medium enterprises. To put the study's hypotheses to the test, 1106 nascent small and medium enterprises that are registered with the National Board for Small Scale Industries were sampled across three major cities in Ghana. Thus, data was gathered from every member of the population. Such data, gathered from the SMEs' financial statements, was submitted to preliminary screening as well as a number of statistical measurements. Operationally, the dependent variable, solvency, was defined as the solvency ratio, working capital ratio, and net worth. As a result, three distinct regression models were developed for robustness. The study's findings broadly indicate that capital structure and profitability have an influence on the solvency of nascent small and medium enterprises. The study also determined that emerging small and medium enterprises should follow the principles of the pecking order theory to reduce the liability of newness. These findings, if adopted by SME owners, can aid in the maturation of their fledgling businesses.
Keywords: Entrepreneurship; New business enterprises

Yönetim kurulu krizleri ve çözüm yolları - Meti̇n, Umut (Kadir Has Üniversitesi, 2021)
YK farklı sorunlar veya uyuşmazlıklarla yüzyüze gelebilir. Sorunlar veya uyuşmazlıklar kriz halini alarak YK'nın işleyişine olumsuz etki edebilmektedir. Kriz derinleştikçe, YK işlevini yerine getirmekte zorlanabilir. Krizin bir adım ötesinde ise YK kilitlenebilmektedir. Pay sahipleri arasındaki menfaat çatışmaları, YK kriz ve/veya kilitlenmesinin en sık rastlanan temel nedenidir. Kilitlenme durumunda, YK toplantı yapamamakta veya karar alamamaktadır. Oysa ki, YK her daim çalışabilmesi gereken bir organdır. YK'nın kilitlenmesi, şirketin de kilitlenmesi sonucu doğurabilir. Bu durum öyle risklidir ki, şirketin feshi/tasfiyesi yakın bir ihtimal olabilmektedir. Bu aşamada kilidin olabildiğince hızlı açılması şirketten menfaati olan herkes için (pay sahipleri, YK üyeleri, çalışanlar, alacaklılar, kamu vb.) hayati önemdedir. Bu nedenle, şirket esas sözleşmesinde YK kriz ve kilitlenmelerine karşı önlemler planlanmalıdır. Tek kişiden ibaret YK modeli ve YK'ya danışma kurulu desteği kilitleme riskine karşı önerdiğimiz modeldir. Pay sahipleri sözleşmesi, aile şirketleri için aile anayasası gibi hukuki metinler kriz ve/veya kilitlenmeye ilişkin tedbirler içermelidir. Önlemlere, rağmen kilitlenme gerçekleşir ise, öncelikle YK içi ve şirket içi çözümler uygulamaya konulmalıdır. Bu tür yöntemler yeterli olmazsa, AUÇY'nin tatbiki, şirket dışından gelen çözümün ilk aşaması olarak kabul edilmelidir. Arabuluculuk ile YK kriz ve kilitlenmelerine karşı etkin, hızlı ve kalıcı çözümler sağlanabilmektedir. "Med-arb" veya "Arb-med" gibi yöntemlerden de faydalanılabilir. Tahkim de bir çözüm yoludur. Bu yolda "seri tahkim usulü" YK kilitlenmeleri için daha uygundur. Son çare olarak nitelediğimiz, dava yolu ise, bazı durumlarda içinde şirketin fesih ve tasfiye riskini barındırdığı için kilidi açmak ve hatta kilidi kırmak için uygulamaya konulabilir. Mahkemelerde, organ yokluğuna dayalı fesih davası ve özellikle haklı sebeple şirketin feshi davası çözüm sağlayabilecek dava tipleridir. Özellikle, haklı sebeple şirketin feshi davası, kriz ve kilitlenmelere daha uygun olup, stratejik sonuçlara da imkân vermektedir. Bunlar yanında, YK işleyişinde yapay zekâdan faydalanmanın mümkün olup olmadığı, yapay zekâya YK üyesi olarak kişi statüsü verilip verilemeyeceği, bu meselenin YK üyelerinin sorumluluğuna etkisi incelenmiştir. Board of Directors may face various disputes or disagreements. These disputes or disagreements may turn into crises which negatively affect the normal functioning of the board. As the crisis deepens, Board of Directors could have difficulties in fulfilling its function. Moreover, a step further from the crisis, Board of Directors might even be locked up. Conflicts of interest among shareholders are known as the most common cause of the board of directors crisis and/or deadlock. In event of a deadlock, Board of Directors, a body should always be able to function, cannot hold meetings or make decisions anymore. The deadlock of board of directors, may lead the entire company to be locked down whereas the company may encounter the possibility of dissolution and liquidation. At this point, unlocking the crisis as quickly as possible is vital for relevant competent persons of the company. Therefore, measures should be taken in the company's articles of association against Board of Director crisis and/or deadlock. One-person Board of Directors model and support of Advisory Board to Board of Directors is the model we recommend against the risk of locking. Legal texts such as shareholder agreements and family constitutions for family companies should include measures regarding deadlock. If a deadlock has occurred in spite of precautions, first of all, Board of Directors and internal remedies should be implemented. If such methods are not sufficient enough, Alternative Dispute Resolution (ADR) methods should be regarded as the first stage of external intervention. Effective and rapid solutions can be achieved against deadlocks via mediation. "Med-arb" or "Arb-med" could be also utilised. Arbitration is also a way and in this way; "expedited (fast-track) arbitration" procedure is more suitable for corporate deadlocks. Litigation, as the last possibility that we propose, could also be applied to unlock or even break the lock, since it contains the risk of dissolution and liquidation of company in some cases. In courts, termination action based on the absence of organs and especially termination of the company with a valid reason are the types of cases that may provide a solution. Especially termination of the company with a valid reason is more suitable for crisis and deadlocks, and also grants strategic results. In addition to these, it has been questioned in this study whether Board of directors possibly benefit from artificial intelligence in the operations and whether AI can be attributed a person-status as a member of Board of Directors. The effects of this issue on the responsibility of the members of Board of Directors have been analysed.
Keywords: Absence of body; Arabuluculuk; Arbitration; Artificial Intelligence; Board directors; Conseil d'administration; Crisis; Deadlock; Inteligência artificial; Intelligence Artificielle; Kilitlenme; Kriz; Mediation; Members of the board directors; Médiation; Organ yokluğu; Tahkim; Yapay zeka; Yönetim kurulu; Yönetim kurulu üyeleri

Les époux et l'entreprise : les aspects matrimoniaux - Blanc, Sonia (Université Paris 2, 2020)
Le mariage entraîne l’application de règles propres aux époux, tandis que l’activité d’entrepreneur provoque également l’application de règles spécifiques à l’entreprise. La présente étude analyse la situation dans laquelle l’un des époux est entrepreneur, mais aussi la situation dans laquelle le conjoint participe à l’entreprise. Le double statut d’époux et d’entrepreneur est source de complexité, car le droit des régimes matrimoniaux et le droit de l’entreprise ont des logiques et des objectifs différents. Il convient donc de les concilier en sauvegardant à la fois l’intérêt des époux et l’intérêt de l’entreprise. Les deux statuts s’adaptent l’un à l’autre ; cependant cela ne se fait pas sans difficultés. De plus, le mariage crée des liens financiers étroits entre les époux et ce quel que soit leur régime matrimonial. Or, l’activité professionnelle d’au moins un des époux au sein de l’entreprise a nécessairement des conséquences sur le plan financier. L’entreprise peut constituer une source de richesse pour les époux. Pourtant elle représente également un risque. De même, la mésentente conjugale constitue un risque dans la mesure où elle peut mettre l’entreprise en péril et ainsi faire perdre des revenus à l’époux entrepreneur. Les époux trouvent au sein du droit des régimes matrimoniaux et du droit de l’entreprise des mécanismes d’organisation permettant de limiter ces divers risques. Ces mécanismes donnent aux époux la possibilité de concilier le statut d’époux et le statut d’entrepreneur. Toutefois nous montrerons que cette liberté reste encadrée.
Keywords: Business law; Collaboration; Commercial law; Conjoint; Corporate law; Droit des affaires; Droit des entreprises en difficulté; Droit des sociétés; Droit des sûretés; Droit rural; Entrepreneuriat; Entreprise; Epoux; France; Insolvency law; Law security; Matrimonial regimes; Rural law; Régimes matrimoniaux; Spouses; Spouses cooperation; Undertaking

L’intervention du juge dans le fonctionnement des sociétés commerciales en droit de l’OHADA - Magne Fosso, Viviane Yolande (Université Côte d'Azur, 2020)
La société commerciale est le cadre par excellence de l’investissement. Soucieux de faire de ce cadre un espace susceptible de répondre aux besoins économiques et sociaux des Etats membres de l’OHADA, le législateur y a apporté une profonde réforme. Dans cette perspective, il a fait du juge l’organe chargé d’assurer l’application effective et efficace des Actes Uniformes et de veiller à la stabilité de l’environnement sociétaire. Il s’agit en effet d’une mission qui lui permet d’intervenir à tous les stades de la vie sociétaire. Cependant, la confrontation entre les pouvoirs des différents acteurs sociaux, la disparité entre les règles de procédure des différents Etats membres de l’OHADA et l’absence de professionnalisme du juge invite à s’interroger sur l’efficacité de cette intervention dans la vie de la société. En réalité, la décision judiciaire et le contrat de société sont deux modes de gestion des rapports sociaux a priori inconciliables. Conformément à la théorie de la nature contractuelle de la société, le juge ne peut influencer la gestion d’un bien privé. Toutefois, les adeptes de la nature institutionnelle de la société ont réussi à apporter des aménagements à ce principe. Ainsi, la protection de l’intérêt social et les impératifs de bon fonctionnement de la personne morale peuvent justifier le développement des pouvoirs judiciaires au sein de la société commerciale. Pourtant, en tant que défenseur de l’intérêt social, les interventions judiciaires demeurent très limitées. Si les nouveaux pouvoirs du juge lui permettent d’être omniprésent au sein de la société commerciale, ceux-ci ne suffisent pas à créer un cadre stable et favorable à l’investissement. De nombreux efforts restent à faire autant sur le plan législatif que dans le cadre de l’organisation des juridictions nationales et la formation professionnelle des juges. Il est question dans cette étude, de déceler les éventuelles limites de l’intervention du juge au sein des sociétés commerciales et d’y proposer les solutions adéquates le cas échéant. L’étude arrive à une double conclusion. D’un côté, l’intervention du juge est insatisfaisante dans la protection de l’environnement sociétaire. Le juge ne dispose pas de mécanismes de régulation adaptés au contexte social. Ainsi par exemple, il ne peut porter atteinte aux droits et pouvoirs sociaux que dans des hypothèses limitativement prévues par la loi, en dépit de l’existence de justes motifs pour agir. Par ailleurs, dans le cadre du recours au contrôle de légalité des actes sociaux, il doit se limiter à un contrôle subjectif qui le conduit à rechercher l’intention de l’auteur de l’acte irrégulier ou abusif, et ne lui permet pas ainsi d’assurer la protection de l’intérêt social. De l’autre côté, l’intervention du juge est insatisfaisante dans la sanction des obligations civiles des acteurs sociaux. En effet, le pouvoir de sanction judiciaire pose des problèmes chaque fois que l’Acte uniforme est muet ou ne donne aucune indication terminologique à partir de laquelle le juge peut retenir son pouvoir. En outre, le juge détient un pouvoir de contrainte très restreint qui ne lui permet pas toujours d’assurer le respect des obligations légales ou les engagements contractuels des acteurs sociaux. The commercial company is the framework par excellence for investment. To make this framework an area likely to meet the economic and social needs of OHADA member states, the legislator has introduced a profound reform. With this in mind, it has made the judge the body responsible for ensuring the effective and efficient application of the Uniform Acts and for ensuring the stability of the corporate environment, a mission which enables it to intervene at all stages of the life of a company. However, the confrontation between the powers of the various social actors, the disparity between the procedural rules of the various OHADA Member States and the lack of professionalism of the judge raises questions about the effectiveness of this intervention in the life of society. Judicial decisions and the partnership contract are in fact two a priori irreconcilable modes of managing social relations. According to the theory of the contractual nature of the company, the judge cannot influence the management of private property. However, the proponents of the institutional nature of the company have succeeded in making adjustments to this principle. Thus, the protection of the corporate interest and the imperatives of the proper functioning of the legal person may justify the development of judicial powers within the commercial company. Yet, as a defender of the social interest, judicial intervention remains very limited. While the new powers of the judge allow him to be omnipresent within the commercial company, they are not sufficient to create a stable and favourable framework for investment. Much remains to be done, both in terms of legislation and in terms of the organisation of national courts and the professional training of judges. This study aims to identify possible limits to judicial intervention in commercial companies and to propose appropriate solutions where necessary. The study comes to a twofold conclusion. On the one hand, the intervention of the judge is unsatisfactory in the protection of the societal environment. The judge does not have regulatory mechanisms adapted to the social context. For example, he can only infringe social rights and powers in cases where the law stipulates that they must be restricted, despite the existence of just grounds for action. Moreover, in the context of recourse to the review of the legality of social acts, he must be limited to a subjective review which leads it to seek the intention of the perpetrator of the irregular or abusive act and thus does not enable him to ensure the protection of the social interest. On the other hand, the judge’s intervention is unsatisfactory in sanctioning the civil obligations of social actors. Indeed, the power to impose judicial sanctions poses problems whenever the Uniform Act is silent or gives no terminological indication from which the judge can retain his power. Moreover, the judge has a very limited power of constraint which does not always enable him to ensure compliance with legal obligations or the contractual commitments of social actors.
Keywords: ABUS; Abuse; Acteurs sociaux; Corporate law; Droit des sociétés; Droit des sociétés commerciales; Judge; Juge; Juges -- Pays de l'OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'OHADA; Social actors

Lei Anticorrupção e direito empresarial: responsabilidade de pessoas jurídicas por atos de corrupção e repressão à corrupção em grupos empresariais - Spercel, Thiago Augusto (Universidade de São Paulo, 2020)
A Lei Anticorrupção Brasileira representou um importante aprimoramento ao microssistema brasileiro de combate à corrupção. Por meio da responsabilização administrativa e civil de pessoas jurídicas pela prática de atos contra a administração pública, as autoridades de combate à corrupção agora podem se socorrer do Direito Administrativo Sancionador para punir a pessoa jurídica corruptora e estimular condutas preventivas de compliance e integridade. Neste estudo, procuramos analisar os pontos de conexão da Lei Anticorrupção Brasileira com o Direito Comercial, incluindo a Lei das Sociedades por Ações, o Código Civil e a Lei de Recuperação de Empresas. Analisamos os limites da responsabilidade objetiva no âmbito do Direito Administrativo Sancionador, a solidariedade do grupo econômico, a desconsideração da personalidade jurídica, o tratamento de passivos de corrupção nos planos de recuperação judicial e a sucessão de multas de corrupção e penas restritivas de direito em reorganizações societárias e aquisição de negócios ou estabelecimentos. Concluímos que as sanções judiciais e administrativas da Lei Anticorrupção Brasileira, por possuírem natureza punitiva, dependem, necessariamente, da verificação de algum tipo de culpabilidade ou reprovabilidade, que pode ser o recebimento de benefícios indevidos, a inobservância do cuidado objetivo necessário ou a falha de organização. Analisamos as hipóteses legais de sucessão das sanções administrativas e judiciais nas reorganizações societárias e, no contexto recuperação judicial de empresas, entendemos que a responsabilização administrativa e civil da Lei Anticorrupção Brasileira não se transmite ao adquirente de unidades produtivas isoladas, e a proteção do art. 60 da Lei de Recuperação de Empresas deve prevalecer. Com relação à responsabilidade solidária do grupo empresarial (sociedades controladoras, controladas, coligadas ou consorciadas), entendemos que essa solidariedade não pode ser automática, mas infelizmente faltam parâmetros legais claros para delimitar seu alcance. Essa falta de parâmetros cria uma insegurança jurídica que pode ser muito negativa para o mundo das operações de aquisições de empresas e trespasse de negócios. Por fim, exploramos a responsabilidade dos financiadores por atos de corrupção, uma vez que, em circunstâncias excepcionais, sanções administrativas e judiciais poderão ser estendidas às instituições financeiras financiadoras de atividades corruptas, os chamados corruptores indiretos. This thesis examines the expulsion, for serious fault, of partners from limited liability companies, provided for in articles 1030, 1085, and 1058 read with 1004 of the Brazilian Civil Code. Despite the subjects enormous importance, and the various studies that exist, the expulsion of partners presents many theoretical and practical difficulties, and there has been no systematic, detailed study of the subject in its various aspects by Brazilian legal scholars. Thus, this work seeks to present a systematic analysis of the subject, constructing an interpretative model that is consistent with the reality of Brazils legal system, addressing questions that have been the subject of little (if any) debate, and suggesting criteria that will ensure that expulsion of partners adequately protects the interests and functionality of the limited liability company and the partners rights. The first chapter analyzes the substantive premise (serious fault) for expulsion of a partner that has breached his duties. The second chapter studies the possible procedures (judicial and non-judicial) for expelling a partner that has committed a serious fault. Lastly, the third chapter addresses the consequences of expulsion of a partner from a limited liability company for serious fault (loss of status socii, calculation and payment of the value of the expelled partners equity interest in the company, treatment given to the quotas held by the expelled partner, and change of the companys name).
Keywords: Anticorruption Law; Corruption Liabilities; Corrupção (Controle); Direito empresarial; Economic group liability; Empresas; Objective liability; Sociedade comercial; Succession

A crise empresarial enquanto situação de pré-insolvência: em particular, a sociedade comercial de responsabilidade limitada em situação de pré-insolvência e os deveres dos administradores - Henriques, Sérgio António Marreiros Coimbra (Universidade Nova de Lisboa, 2020)
The concept of “pre-insolvency situation” aggregates different legal norms that require harmonization in the context of a situation of business crisis, even if that situation might not still be one of the situations normatively recognised by legislation, as is the case, for example, in Portugal, of the “difficult economic situation” or the “situation of insolvency”. Simultaneously, within the existing legal framework, business continuity is generally seen as preferable to business destruction, since value (and the ability to generate it) goes beyond asset value, arising also from the specific organisation of resources (financial, human, know-how and others) contained in the business at that time. However, since recovery is not only linked to the evaluation of a business activity’s viability, but, also, to the individual interests of each creditor, the “pre-insolvency situation” prompts several challenges, subject to analysis in this study. Due to the preponderance of limited liability companies as the vehicle for business activity, the effect of the “pre-insolvency situation” in the fiduciary duties of directors of those companies is also studied. From the existing legal rules I identify an answer to the conflict of interests between corporate stakeholders specific to that situation, in order to propose a legal mechanism incident on management, who can act towards the resolution of possible incompatibilities in a manner that is timely in terms of promoting business continuity, in order to ensure the correction (or appropriateness) of the decision making process used in that situation, therefore preventing recalcitrant, opportunistic or abstentionist behaviours that have a negative impact in the company’s asset composition. The combined analysis of Corporate Insolvency Law – including the Directive (EU) 2019/1023, of 20 June 2019, on restructuring and insolvency - and Corporate Law, is supplemented by the consideration of the legal effects derived from this coexistence, namely in terms of creditor behaviour (aimed to defend their individual rights as a claimant) and the behaviour of shareholders and other intervening actors. It’s in this context that I claim that the contents of the fiduciary duties of directors know refractions that are exclusive to the “pre-insolvency situation”, a configuration of their duties directed at alleviating the effects of potential abuses that would be made possible if their function could be performed without any type of limitation and, also, at enhancing behaviours that promote business continuity or, at least, minimize the consequences of a possibly forthcoming “situation of insolvency”. To this extent, one of the prices of director’s discretion is monitoring business viability, structuring the company to identify the “pre-insolvency situation” and weigh the reaction to the challenges it places. O conceito jurídico de situação de pré-insolvência, construção de base doutrinária, congrega normas jurídicas dispersas que carecem de harmonização no contexto da verificação de uma situação de crise empresarial, mesmo que esta possa ainda não corresponder às situações tipificadas pela legislação, de que são exemplo, em Portugal, a situação económica difícil ou, até, a situação de insolvência. Simultaneamente, no quadro legal vigente, a continuidade da atividade empresarial afirma-se, em geral, preferível à sua destruição, já que o valor de uma empresa (e a capacidade de o gerar) vai além do seu valor patrimonial, decorrendo também da particular organização de recursos (financeiros, humanos, saber-fazer e outros) nela contidos naquele momento. No entanto, a recuperação da empresa não está apenas ligada à avaliação da viabilidade da sua atividade empresarial, mas, também, aos interesses individuais de cada credor, pelo que a situação de pré-insolvência suscita vários desafios, sujeitos a análise neste estudo. Reconhecendo a preponderância das sociedades comerciais de responsabilidade limitada na atividade empresarial, identifica-se, ainda, o efeito da verificação de uma situação de pré-insolvência nos deveres dos membros dos órgãos de administração dessas sociedades. Retiro do direito em vigor a resposta ao conflito de interesses entre intervenientes societários próprio dessa situação para propor um mecanismo jurídico incidente sobre a administração. Esta pode atuar no sentido da resolução de eventuais incompatibilidades em tempo útil à promoção da continuidade da atividade empresarial, por forma a assegurar a correção (ou adequação) do processo de formação de decisões empresariais utilizado nessa situação, assim impedindo condutas recalcitrantes, oportunistas ou abstencionistas que tenham relevo negativo na composição do património social. À análise conjugada das normas de Direito da Insolvência em contexto empresarial - onde se inclui a Diretiva (UE) 2019/1023, de 20 de junho de 2019, sobre reestruturação e insolvência – e de Direito das Sociedades Comerciais, acresce a consideração dos efeitos jurídicos desta convivência, em particular na conduta negocial dos credores (dirigida à defesa individual dos seus direitos de crédito) e na conduta dos titulares do capital social e outros intervenientes com relevância para a sociedade. É neste contexto que afirmo refrações no conteúdo dos deveres gerais dos administradores próprias da situação de pré-insolvência, uma configuração dos seus deveres dirigida a mitigar os efeitos de potenciais abusos que o exercício da sua função sem quaisquer limites no contexto de uma crise empresarial poderia gerar e, ainda, a potenciar condutas predispostas à continuidade da atividade empresarial ou, pelo menos, à minimização das consequências da eventual declaração da situação de insolvência. Nesta medida, entre os preços da discricionariedade dos administradores está o da vigilância da viabilidade da atividade empresarial, estruturando a sociedade para a identificação da situação de pré-insolvência e ponderando a reação aos desafios por esta colocados.
Keywords: Administrateur; Faillite; Insolvency; Société à responsabilité limitée

Direito de recesso e valor justo como proteção do investidor: a reforma necessária - Ponczek, Daniel Kalansky (Universidade de São Paulo, 2020)
Este trabalho parte da seguinte indagação: qual seria o melhor critério de avaliação para calcular o reembolso para fins de recesso do acionista minoritário dissidente de uma sociedade por ações? A análise partiu da constatação de que a atual Lei das Sociedades por Ações (Lei nº 6.404 de 1976), conforme entendimento majoritário, fixa como método de cálculo o patrimônio líquido contábil, quando o estatuto social não determina que outro seja aplicado. Contudo o método nem sempre reflete o valor justo da companhia, o que faz com que ao acionista seja ofertado um valor irrisório. Para estudar esse tema, começou-se por analisar a origem e os propósitos para os quais o recesso foi criado. Em seguida, analisaram-se os métodos de cálculo disponíveis para avaliar uma companhia. Estudou-se, também, a maneira como o reembolso é calculado nos Estados Unidos da América e na Itália. Com esse arcabouço teórico, analisou-se o direito brasileiro e, ao final, delineou-se como seria o valor de reembolso ideal. Concluímos pela necessidade de uma reforma legislativa de forma a prever que o valor do recesso deve dar-se obrigatoriamente pelo valor justo e, assim, oferecer proteção ao acionista minoritário e fomentar o mercado de capitais.
Keywords: Acionista minoritário; Appraisal remedy; Appraisal right; Corporate law; Direito de recesso; Essential right of the shareholder; Fair value; Investisseur (protection); Investments; Investor protection; Protection for the minority shareholders; Reembolso; Reimbursement; Right to dissent; Rétractation; Sociedade por ações; Valuation methods

Contribuições para a análise do poder de influência dos credores na recuperação judicial - Navarro, Norlan Moreira (Universidade de São Paulo, 2020)
A presente tese visa a analisar a recuperação judicial com a finalidade de apresentar contribuições para o estudo do papel de influência dos credores na recuperação judicial em decorrência do ambiente normativo estabelecido a partir da rede de direitos e deveres instituída na legislação em vigor no Brasil. Uma vez iniciada a recuperação judicial, diversas decisões dependerão da concordância da coletividade de credores, sendo a mais importante delas a aprovação do plano de recuperação, realidade que permite o surgimento de credores com grande poder na negociação do plano de recuperação com a devedora. Sem a pretensão de esgotar o assunto, o presente estudo tem quatro grandes núcleos. O primeiro deles é histórico e analisa tanto a evolução econômica do Brasil quanto as diversas legislações que já vigoraram no país em matéria de falência e recuperação judicial. O segundo núcleo analisa o próprio instituto da recuperação judicial atualmente em vigor, onde há o exame de suas regras, bem como o papel dos diversos agentes que atuam e contribuem para o procedimento recuperacional. Adiante, no terceiro núcleo, há a análise do paradigma do controle interno e do controle externo. Finalmente, o quarto e último núcleo tece as contribuições sobre o papel que alguns credores podem assumir em relação à empresa em recuperação judicial, desde que reunidas certas condições específicas. O estudo é motivado pela relevância que a recuperação judicial tem apresentado na realidade societária brasileira, bem como pela observação empírica de que determinados credores, ao negociarem o plano de recuperação com uma empresa em crise, possuem maior vantagem que outros credores, situação que merece ser delimitada e estudada, até para fins de atribuição de deveres e responsabilidades a tais credores.
Keywords: Assembleia de credores; Control; Corporate reorganization; Cram down; Creditor; Créancier; Dominant influence; External control; Falência; Pouvoir d'influence; Recouvrement judiciaire; Recuperação judicial; Structured bargaining

Les nullités en droit des sociétés commerciales - Ramarde, Nedoumbaiel (Université Cheikh Anta Diop, 2020)
Les nullités sont des sanctions des irrégularités de forme ou de fond, des actes juridiques. Ces sanctions ont essentiellement pour fonctions la prévention, la garantie de l'ordre public de direction et de protection. Elles participent à l'effectivité et à l'efficacité de la règle de droit. Le législateur OHADA, dans le souci d'assainir le climat des affaires et les relations contractuelles, privilégie les nullités textuelles dans l' AUSCGIE. La nullité de la société est strictement textuelle et celle des actes ou délibération est mixte, c'est-à-dire textuelle et virtuelle. Cependant, il faut noter que dans l'analyse des causes de nullités, il apparaît une certaine incohérence. Certains actes interdits, la fictivité de la société, sont tantôt sanctionnés par la nullité, tantôt par l'inexistence. Le non-respect de certaines autorisations préalables est, d'une part, sanctionné par l'inopposabilité, d'autre part, par la nullité. La violation des règles pénales n'est pas expressément sanctionnée par la nullité et la jurisprudence sanctionne tantôt par la nullité virtuelle, tantôt refuse de sanctionner par la nullité virtuelle alors qu'il s'agit de la violation d'une règle impérative. Il résulte de cette analyse une difficulté à une sanction dynamique dû à l'esprit d'impérativité de l'article 2 et du système de nullité textuelle. Dans l'analyse de la mise en œuvre des nullités, la primauté de la protection des intérêts économique au travers le mécanisme de la régularisation d'office, fragilise cette sanction. Le législateur admet la nullité judiciaire qu'à titre exceptionnelle. Mais le contentieux conventionnel de la nullité n'est qu'implicitement admis. La subdivision nullité facultative et obligatoire n'est pas cohérente au critère de l'intérêt protégé. Il en résulte une absence du régime uniforme. La régularisation, les effets non rétroactifs de nullité, les brèves prescriptions et l'inopposabilité de nullité aux tiers sont suffisants pour se passer du principe pas de nullité sans texte en droit des sociétés commerciales.
Keywords: Droit des sociétés commerciales; Liberté contractuelle; Nullités; Pouvoir du juge; Responsabilité des dirigeants

Dever de lealdade dos acionistas nas sociedades anônimas - Amaral, José Romeu Garcia do (Universidade de São Paulo, 2020)
O tema desenvolvido na tese refere-se ao dever de lealdade dos acionistas nas sociedades anônimas. Os acionistas, a partir da aquisição da participação social, sujeitam-se ao ordenamento societário e enquadram-se em uma situação jurídica capaz de qualificar-se como posição ou estado (o status socii), abrangendo componentes ativos (direitos e poderes) e passivos (deveres, obrigações e sujeições). O dever de lealdade, portanto, pertence aos componentes passivos da posição jurídica e impregnam as relações entre os acionistas e entre estes e a companhia, tendo por fundamento a boa-fé objetiva (arts. 113, 187 e 422 do CC). Muito se estudou sobre os direitos e poderes, porém pouca atenção foi dada aos deveres dos acionistas. No Brasil, este tema não foi objeto de estudo monográfico específico. A tese pretende, assim, sistematizar a matéria e oferecer contribuição original para o seu desenvolvimento. Dividida em cinco partes, a primeira apresenta os fundamentos do dever de lealdade, abrangendo a noção de lealdade, a relação societária e seus elementos, a situação jurídica do acionista, o desenvolvimento do tema no direito estrangeiro e as suas fontes normativas. A segunda identifica o enunciado geral do dever de lealdade nas companhias, destacando a sua função e tipologia (deveres de lealdade positivos e negativos). Na terceira, aborda as situações específicas de sua aplicação, conforme a qualificação jurídica do acionista (controlador ou não controlador). A quarta parte trata da responsabilidade do acionista e das consequências jurídicas decorrentes da violação do dever de lealdade. A quinta e última parte encerra a tese com as considerações finais e a apresentação de singela proposta de aprimoramento da legislação societária. The subject developed in this thesis refers to the duty of loyalty of shareholders in corporations. Shareholders, from the acquisition of shares, are subject to the corporate law framework and fit into a legal situation capable of qualifying as position or state (the status socii), covering active (rights and powers) and passive (duties, bonds and subjecting) components. The duty of loyalty, therefore, belongs to the passive components of the legal position and impregnate the relations among the shareholders and among them and the company, being based in an objective bona fides (arts. 113, 187 and 422 of Civil Code). About rights and powers much has been studied, however little attention was given to the duties of shareholders. In Brazil, this theme was not subject of a specific monographic study. Thus, the thesis intends to systematize the subject and to provide an original contribution to its development. Divided into five parts, the first presents the fundamentals of the duty of loyalty, covering the notion of loyalty, the corporate relationship and its elements, the legal situation of a shareholder, the theme development in foreign law and its normative sources. The second identifies the general mentioned of the duty of loyalty in the companies, highlighting their function and typology (positive and negative duties of loyalty). In the third, it addresses the specific situations of its enforcement, according to the legal shareholder qualification (controlling or non-controlling). The fourth part addresses the responsibility of a shareholder and the legal consequences of breaching the duty of loyalty. The fifth and last part concludes the thesis with the final considerations and the presentation of a proposal for the improvement of the corporate law.
Keywords: Acionistas; Actionnaire; Boa-fé objetiva; Corporate law; Corporate relationship; Corporation; Dever de lealdade; Duties; Duty of loyalty; Fair Dealing; Loyalty; Loyauté; Objective bona fides; Relação societária; Shareholders; Sociedade anônima; Sociedade comercial

Reflexos das novas tecnologias nas assembleias de S/A - Nascimento, João Pedro Barroso do (Universidade de São Paulo, 2020)
Ao longo dos últimos anos, relevantes transformações no regime jurídico das Assembleias Gerais e do exercício do direito de voto ocorreram no Brasil e no mundo. É cada vez mais frequente a adoção de sistemas de votação a distância e participação remota em Assembleias Gerais, bem como a utilização de elementos de tecnologia para aperfeiçoar os procedimentos em pedidos públicos de procuração e em outros aspectos das Assembleias Gerais. Nesse sentido, a LSA foi alterada pela Lei nº 12.431/2011, que promoveu as inclusões: (i) do artigo 121, parágrafo único, da LSA, a fim de reconhecer e legitimar, nas companhias abertas, a possibilidade de participação e voto a distância dos acionistas em Assembleia Geral; e (ii) do artigo 127, parágrafo único, da LSA, que considera presente em Assembleia Geral o acionista que registrar a sua presença a distância. Adicionalmente, as regulações e atos normativos da CVM também têm sido revistos, destacando-se - por exemplo - a Instrução CVM nº 481/2009, com diversas alterações recentes. Alguns países modernizaram a forma como as Assembleias Gerais são realizadas, admitindo encontros não presenciais, nos quais a interação entre os participantes do conclave é realizada apenas remotamente. Entendemos que a adoção de tecnologias nas Assembleias Gerais é bem-vinda e deve ser feita como uma forma de ampliação de horizontes, e não como um limite ao exercício de direitos. Sem prejuízo, somos contrários à redução das Assembleias Gerais a encontros exclusivamente virtuais (não presenciais) onde não ocorram debates e discussões e/ou com limitações de interação entre participantes presenciais. Tradicionalmente, as Assembleias Gerais desempenham um importante papel, na medida em que permitem que os acionistas se envolvam e monitorem coletivamente os negócios sociais, por meio de 3 (três) funções em especial: (i) Função de Informação: os acionistas recebem da companhia informações sobre relevantes e diversos temas pertinentes à companhia e à sua atividade; (ii) Função de Fórum: é oferecido aos acionistas um local para discussões e formulação de questões pertinentes à companhia; e (iii) Função de Tomada de Decisões: os acionistas reúnem-se para, coletivamente, tomar decisões e formar a vontade social. Estas 3 (três) funções têm sofrido importantes transformações recentes e, indiscutivelmente, precisam ser repensadas, a fim de evitar a obsolescência do Direito Societário. É inconcebível pensar que os avanços tecnológicos não produzirão reflexos nas relações entre os acionistas, os administradores e/ou na dinâmica organizacional das grandes companhias. Diante dessas mudanças, tornam-se essenciais estudos dedicados à compreensão de institutos clássicos do direito societário brasileiro, a partir do cenário da Quarta Revolução Industrial. Portanto, a análise da aplicação das tecnologias às Assembleias Gerais de sociedades anônimas é inovadora e de extrema relevância para a comunidade jurídica e para o mercado de capitais, pois o desenvolvimento tecnológico tem potencial para encurtar distâncias entre acionistas, colaborar para o ativismo societário e contribuir para o combate ao absenteísmo - alterando as práticas societárias e, consequentemente, impulsionando mudanças legislativas e jurisprudenciais. Sendo assim, este trabalho tem como objetivo oferecer as seguintes contribuições originais à ciência jurídica: (i) de forma imediata - analisar os reflexos nas Assembleias Gerais das mudanças promovidas pelos mecanismos de voto e participação a distância e, também, pelas modificações nos pedidos públicos de procuração (cf. artigos 121, parágrafo único, e 127, parágrafo único, da LSA e Instrução CVM nº 481/2009); e (ii) de forma mediata - ponderar sobre os potenciais efeitos a serem obtidos com a adoção de tecnologias e mecanismos modernos nas Assembleias Gerais, como blockchains e smart contracts, a fim de reduzir a necessidade de atuação humana em aspectos burocráticos do procedimento assemblear. Este trabalho também analisará algumas adequações sistêmicas a serem realizadas na legislação societária, de modo a adequá-la ao padrão evolutivo e viabilizar a adoção de tecnologias nas Assembleias Gerais. A relevância do presente trabalho reside na colaboração para compreensão das atuais tendências e novas formas de exercício de direitos de acionistas no âmbito das companhias abertas, de modo a (i) identificar obsolescências na legislação societária atual; e (ii) auxiliar na elaboração de atualizações e revisão da legislação societária brasileira, à luz das novas tecnologias.
Keywords: Absenteeism; Agency problems; Alemanha; Assembleia geral; Blockchain and smart contracts; Capital market; Corporate governance; Corporate law; Corporate structure and economic development; Digital law; Direito comparado; Espanha; França; Governança corporativa; Grã-Bretanha; Holanda; Itália; Nouvelles technologies; Portugal; Public proxy solicitations; Publicly-owned and privately-owned corporations; Remote voting; Réunion; Shareholder's activism; Shareholder's general meetings; Sociedade anônima; Société Anonyme; Société commerciale; Technology and innovation; Tecnologia da comunicação; Tecnologia da informação

Dano ao acionista: contribuições à Teoria da Responsabilidade Societária - Weber, Ana Carolina (Universidade de São Paulo, 2020)
Os reflexos de práticas de corrupção na esfera patrimonial das companhias abertas e de seus acionistas deram margem, nos últimos anos, a questionamentos sobre a caracterização de danos e de sua imputação aos administradores. O aumento do ativismo e da litigância societária fazem com que se tenha que retomar conceitos elementares à teoria da responsabilidade societária. Nesse sentido, analisa-se os elementos caracterizadores da relação entre administradores e companhias abertas, com o intuito de identificar as hipóteses em que o patrimônio pessoal dos administradores pode vir a responder por atos praticados no exercício de seus cargos. Verificado o fundamento para a imputação da obrigação de indenizar aos administradores, examina-se as formas pelas quais a reparação pode ser obtida, estudando-se mecanismos como ação civil pública, o termo de compromisso e as ações judiciais e os procedimentos arbitrais. Por se tratar de responsabilidade patrimonial, examina-se o patrimônio como o objeto do dano, fazendo-se remissão a entendimentos da doutrina de direito civil confrontados com pronunciamentos do direito das sociedades anônimas. Busca-se definir a partir daí a linha divisória entre os danos que podem ser recuperados, de forma direta, pela companhia aberta e aqueles que poderão ser objeto de pleitos reparatórios formulados pelos acionistas em face dos administradores. Effects of corruption practices in the publicly-held corporations and their shareholders' assets have led, in recent years, to questions about the characterization of damages and their attribution to the corporate managers. The rise of activism and corporate litigation obliges one to return to elementary concepts of the corporate liability theory. In this sense, we analyze the elements that characterize the relationship between managers and publicly-held corporations, in order to identify the hypotheses in which managers' personal assets may be held responsible for acts performed in the exercise of their positions. Having verified the grounds for attributing administrators the obligation to indemnify, we examine the ways in which compensation can be obtained by examining mechanisms such as public civil action, the consent decrees and lawsuits and arbitral proceedings. Because it refers to civil liability, the estate is examined as the object of the damage. We refer to the understandings of civil law scholars, confronted with understandings of corporate law scholars. From this, we seek to define the dividing line between the damages that may be directly recovered by the publicly-held corporations and those that may be the object of claims filed by the shareholders before the managers.
Keywords: Administração de recursos patrimoniais; Corporate law; Damages; Dano patrimonial; Direct Damages; Directors and Officers; Estate; Indirect Damages; Publicly-held Corporations; Recoverable methods; Reparação do dano; Responsabilidade patrimonial; Sociedade anônima de capital aberto

An Empirical Analysis of Private Equity Investment Affecting Enterprise Value - Li, Jianhong (Université de Genève, 2020)
The lack of long-term and stable financial support for SMEs is the fundamental reason why enterprises cannot develop for a long time. At present, the situation of financing difficulties for SMEs is becoming more and more serious. Private equity (PE) investment has emerged as an important financing method. Private equity investment, while broadening the financing channels of SME capital markets, brings advanced management experience to enterprises, which helps enterprises to develop rapidly and effectively. According to the statistics of the Zero2IPO Research Center, the active investment institutions in China's equity market have grown from more than 200 in 2000 to more than 14,000 in 2018, with a total asset under management over RMB 9 trillion. Great progress has been realized in the scale and development of the industry. In addition, with the launch of the GEM in 2009, PE investment industry met new opportunities of development and became popular. At present, the development of China's PE investment business is still at an early stage. Neither relevant policies, laws and regulations nor supporting mechanisms are mature enough. Therefore, researches on China's PE investment business needs to be carried out. In this context, more and more scholars are beginning to focus on the field of PE investment. This paper focuses on whether PE investments can fundamentally increase the enterprise value. The basic theory is sorted out to serve as the theoretical basis for this study. Through a systematic analysis, this paper draws out 4paths of PE investment affecting enterprises, which are the influence on technological innovation, corporate governance activities, dividend distribution decision and earnings management, respectively. And through empirical analysis, it finds the empirical basis of the impact of PE investment on enterprise value, and investigates how PE investments affect enterprise value based on the difference in investment characteristics such as investment duration and whether the investment is joint or not. This paper conducts an empirical test by selecting the listed companies of the Shenzhen Stock Exchange GEM in 2015-2018 as sample. The results show that the investment of PE firm will significantly increase the value of the target enterprise. This paper makes a detailed analysis of sample data. The conclusion of the study is that private equity investment will have a significant impact on the value of target enterprises. Private equity investment plays an important role in the modern governance structure of small and medium-sized enterprises in China This paper enriches the existing literature and provides constructive suggestions for the health development of the PE investment market. 中小企业缺乏长期稳定的资金来源是企业无法长久发展的根本性原因，目前 中小企业融资难的形势越来越严峻，私募股权投资作为一种重要的融资手段应运 而生。私募股权投资在拓宽中小企业资本市场融资渠道的同时，给企业带来先进的 管理经验，有助于企业快速并有效的发展。据清科研究中心的统计数据显示，中国 股权市场活跃的投资机构已由 2000 年的 200 多家发展到 2018 年的 1.4 万多家，管 理资本量超过 9 万亿人民币，行业规模和发展实现了质的飞跃。此外，随着 2009 年创业板的推出，私募股权投资行业的发展业迎来了新的希望和契机，私募股权投 资业务开始盛行。目前，我国私募股权投资业务的发展还处于早期阶段，无论是从 政策还是法律法规再到配套机制，都还不够健全。因此，对我国私募股权投资业务 的研究亟需开展，在此背景下，越来越多的学者开始关注私募股权投资这一领域。 本文研究的重点是私募股权投资是否能够根本上提升企业价值。本文首先对 基础理论进行了梳理，以此作为研究的理论依据，而后论述了私募股权投资对被投 资企业价值影响的理论分析，。本文通过系统的理论分析得出了私募股权投资影响 企业的路径，并通过实证分析，得到私募股权投资对企业价值的影响的实证依据， 并且从投资期限和是否联合投资等投资特征的差异性，深入研究私募股权投资对 企业价值的影响方式。本文通过选取深圳证券交易所创业板 2015-2018 年的上市企 业作为样本，进行了实证检验，并得出以下研究结论:私募股权投资的参与会显著 提升目标企业的价值，同时，私募股权投资的期限越长、联合投资机构的数量越多， 目标企业的价值也会越高。 本文基于理论又结合实际，对样本数据进行了分析，研究的结论是私募股权投 资会对被投资企业的价值产生显著影响。私募股权投资对于我国中小企业的现代 化治理结构起到了完善作用。本文的研究结果丰富了现有文献，对私募股权投资市 场健康发展提出了建设性的建议。
Keywords: Enterprise Value; Investment Term; PE Investment

Anonim ortaklıklar hukukunda esas sözleşme özgürlüğü ve sınırları - Vezi̇roğlu, Cem (İstanbul Üniversitesi, 2020)
Bu doktora tezi, anonim ortaklıklar hukukunda esas sözleşme özgürlüğü ve bunun sınırlarının çeşitli açılardan incelenmesini konu almaktadır. Üç bölümden oluşan tezin ilk bölümü konunun kuramsal çerçevesini çizmeyi hedeflerken, ikinci ve üçüncü bölümler ise mevcut sorunlar karşısında dogmatik hukuk bakımından çözümler geliştirmeyi amaçlamaktadır. Bu kapsamda öncelikle özel hukukta ve ortaklıklar hukukunda sözleşme özgürlüğünün kavramsal, teorik, tarihsel, anayasal, ekonomik ve ahlaki zemini ortaya koyulmuştur. İkinci bölümde sözleşme özgürlüğünün anonim ortaklıklar hukukundaki görünümü ele alınmış ve bunu hayata geçiren en önemli işlem olan esas sözleşme çeşitli açılardan irdelenmiştir. Son bölümde ise esas sözleşme özgürlüğünün genel hükümler ve anonim ortaklıklar hukuku çerçevesindeki sınırları incelenmiştir. Bu bağlamda TK m. 340 hükmünde düzenlenen emredici hükümler ilkesine özel bir önem atfedilmiştir. Çalışmada disiplinler arası yöntemin esas alınması doğrultusunda ortaklık teorilerine ve hukukun ekonomik analizine başvurulmuştur. Anılan yöntemlerin katkısı hem pozitif hukuk hem de hukuk politikası açısından ortaya koyulmuştur. Ayrıca incelemede karşılaştırmalı hukuka ve tarihsel araştırmaya geniş yer ayrılmıştır. This doctoral thesis analyzes contractual freedom in articles of association and its limits in joint stock companies from various aspects. The thesis consists of three parts. While the first part aims to set the theoretical framework of the problem, the second and third parts intend to find solutions vis-à-vis existing problems in terms of positive law. Within this scope conceptual, theoretical, constitutional, economic and ethical aspects of contractual freedom in private law and corporate law are primarily examined. The second part deals with contractual freedom in corporate law and examines articles of association from various perspectives as it is the most important legal act that brings contractual freedom into being. The last part analyzes the limits of contractual freedom in articles of association pursuant to general provisions of civil law and joint stock company law. In this regard, the principle of mandatory norms stipulated in Turkish Commercial Code numbered 6102 Article 340 is attached a particular importance. Theories of the corporation and economic analysis of law are applied in accordance with the interdisciplinary methodological view adopted in this study. Contribution of the mentioned methods are set forth in terms of both positive law and legal policy. Moreover, comparative legal analysis and historical analysis are used extensively.
Keywords: Anonim ortaklıklar; Anonim şirketler; Commercial law; Company law; Contracts; Contractual freedom; Emredici norm; Incorporated companies; Joint stock company; Peremptory norms; Sözleşme özgürlüğü; Sözleşmeler; Ticaret hukuku; Şirketler hukuku